Optical film and flexible display device
The optical film with a polyimide-based resin and specific structural units addresses folding resistance and yellowness issues, ensuring high folding frequency and low yellowness for improved visual recognition and reduced power consumption in flexible display devices.
Patent Information
- Application Number
- CN202080074893.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2020-10-09
- Filing Date
- 2020-10-22
- Publication Date
- 2024-12-17
- Estimated Expiration
- 2040-10-22
AI Technical Summary
Optical films containing polyimide resins for flexible display devices require improved folding resistance and low yellowness to maintain mechanical strength and visual clarity during repeated bending.
The optical film is formulated with a polyimide-based resin having a yield strength of 81 MPa or more, a yellowness index of less than 3.0, and specific structural units represented by formulas (1) and (3) to enhance folding resistance and reduce yellowness.
The film achieves excellent folding resistance with a folding frequency of 80,000 times or more and low yellowness, improving visual recognition and reducing power consumption by maintaining high light transmittance.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] The present invention relates to an optical film containing a polyimide-based resin and a flexible display device having the optical film. Background Art
[0002] Display devices such as liquid crystal display devices and organic EL display devices are widely used in various applications such as mobile phones and smart watches. Glass is used as the front panel of such display devices, but glass is very rigid and easily broken, so it is difficult to use as a front panel material for flexible display devices. Therefore, as one of the materials to replace glass, optical films using polymers such as polyimide resins and polyamide-imide resins have been studied (Patent Documents 1 and 2).
[0003] Prior art literature
[0004] Patent Literature
[0005] Patent Document 1: International Publication No. 2014 / 046180
[0006] Patent Document 2: International Publication No. 2016 / 152459 Summary of the invention
[0007] Problems to be solved by the invention
[0008] When an optical film containing a polyimide resin is used in a flexible display device, for example, the optical film is required to have high folding resistance so that the optical properties and mechanical strength of the optical film do not change due to repeated bending. Various optical films containing polyimide resins are known in the past, but the folding resistance of the optical film is required to be further improved.
[0009] In addition, in a flexible display device, an optical film including a polyimide-based resin used as a front panel is required to have not only high folding resistance but also low yellowness.
[0010] Therefore, an object of the present invention is to provide an optical film having low yellowness and excellent folding resistance.
[0011] Means for solving problems
[0012] The present inventors have conducted intensive studies to solve the above-mentioned problems and, as a result, have found that the folding resistance can be improved when the yield strength of the optical film is within a predetermined range, thereby completing the present invention.
[0013] That is, the present invention includes the following preferred embodiments.
[0014] [1] An optical film comprising a polyimide-based resin, the optical film having a yield strength of 81 MPa or more in a tensile test and a yellowness index of less than 3.0.
[0015] [2] The optical film according to [1] above, wherein the elastic modulus is 4.8 GPa or more.
[0016] [3] The optical film according to [1] or [2] above, wherein the total light transmittance is 85% or more.
[0017] [4] The optical film according to any one of [1] to [3] above, wherein the weight average molecular weight of the polyimide resin is 100,000 or more.
[0018] [5] The optical film according to any one of [1] to [4] above, wherein the polyimide resin comprises a structural unit represented by formula (1),
[0019] [Chemical formula 1]
[0020]
[0021] [In formula (1), Y represents a tetravalent organic group,
[0022] X represents a divalent organic group,
[0023] * indicates bonding end],
[0024] As Y in formula (1), the structure represented by formula (2) is included,
[0025] [Chemical formula 2]
[0026]
[0027] [In formula (2), R 1 independently represent a halogen atom, an alkyl group which may have a halogen atom, an alkoxy group, an aryl group or an aryloxy group,
[0028] R 2 ~R 5 independently represent a hydrogen atom or a monovalent hydrocarbon group which may have a halogen atom,
[0029] m independently represents an integer from 0 to 3,
[0030] n represents an integer from 1 to 4,
[0031] * indicates a bonding end, where R 2 ~R 5 In at least one benzene ring, R 2 ~R 5 At least one of them is a monovalent hydrocarbon group which may have a halogen atom].
[0032] [6] The optical film according to any one of [1] to [5] above, wherein the polyimide-based resin is a polyamide-imide resin.
[0033] [7] The optical film according to any one of [1] to [6] above, wherein the polyimide resin comprises a structural unit represented by formula (3),
[0034] [Chemical formula 3]
[0035]
[0036] [In formula (3), Z and X independently represent a divalent organic group,
[0037] * indicates bonding end].
[0038] [8] The optical film according to [7] above, wherein the polyimide resin contains a structure represented by formula (4) as Z in formula (3),
[0039] [Chemical formula 4]
[0040]
[0041] [In formula (4), W independently represents a single bond, -O-, a diphenylmethylene group, a divalent hydrocarbon group which may have a halogen atom, -SO 2 -、-S-、-CO-、-PO-、-PO 2 -、-N(R W1 )-or-Si(R W2 ) 2 -, R W1 and R W2 independently represent a hydrogen atom or an alkyl group which may have a halogen atom, R 8 independently represent a halogen atom, an alkyl group which may have a halogen atom, an alkoxy group, an aryl group or an aryloxy group,
[0042] p independently represents an integer from 0 to 4,
[0043] q represents an integer from 0 to 4,
[0044] * indicates bonding end].
[0045] [9] The optical film according to any one of [1] to [8] above, which is a film for a front plate of a flexible display device.
[0046]
[10] A flexible display device comprising the optical film according to any one of [1] to [9] above.
[0047]
[11] The flexible display device according to
[10] above, further comprising a touch sensor.
[0048]
[12] The flexible display device according to
[10] or
[11] , further comprising a polarizing plate.
[0049] Effects of the Invention
[0050] According to the present invention, an optical film having low yellowness and excellent folding resistance can be provided. DETAILED DESCRIPTION
[0051] Hereinafter, embodiments of the present invention will be described in detail. It should be noted that the scope of the present invention is not limited to the embodiments described herein, and various modifications can be made without departing from the gist of the present invention.
[0052] 〔Optical film〕
[0053] The optical film of the present invention is an optical film comprising a polyimide-based resin, wherein the yield strength of the optical film in a tensile test is 81 MPa or more and the yellowness is less than 3.
[0054] The yield strength of the optical film of the present invention in a tensile test is 81 MPa or more. When the yield strength is less than 81 MPa, the folding resistance of the optical film cannot be fully improved. The yield strength is preferably 83 MPa or more, more preferably 85 MPa or more, further preferably 88 MPa or more, further preferably 90 MPa or more, particularly preferably 93 MPa or more, and particularly preferably 95 MPa or more. From the perspective of the stress required for bending, it is preferably 300 MPa or less, more preferably 250 MPa or less, and further preferably 200 MPa or less.
[0055] In this specification, the yield strength in a tensile test means the yield strength by offset method measured by ASTM D638-14. Specifically, it can be obtained by drawing a line parallel to the straight line portion at the beginning of the test from a point on the strain axis corresponding to a permanent strain of 0.2% in the stress-strain curve, and then obtaining the yield strength from the stress indicated by the point where the line intersects with the above curve. The yield strength can be measured, for example, using a tensile testing machine in accordance with Section A2.6 of ASTM D638-14. As a measuring method, for example, the method described in the Examples can be used.
[0056] As physical properties that can affect the resistance of the optical film to bending, various physical properties such as elastic modulus have been studied, and it is known that sufficient folding resistance may not be achieved only by increasing the elastic modulus. Therefore, in order to further improve the folding resistance, the present inventors have studied various physical properties, and as a result, it is known that the folding resistance can be sufficiently improved when the yield strength in the tensile test is 81 MPa or more. As a method for adjusting the yield strength to the above range, there is no particular limitation, and a method using a polyimide resin as described later can be cited.
[0057] In addition, the yellowness (hereinafter, sometimes described as YI value) of the optical film of the present invention is less than 3.0. When the YI value is 3.0 or more, the YI value of the optical film is too high, and therefore, the visual recognition when visually recognizing, for example, an image through the optical film is reduced. From the viewpoint of easily improving the visual recognition of an image through the optical film, the YI value of the optical film of the present invention is preferably 2.8 or less, more preferably 2.6 or less, further preferably 2.5 or less, preferably -5 or more, and more preferably -2 or more. If the YI value of the optical film is below the above upper limit, the transparency becomes good, and in the case of a front panel for a display device, it can contribute to high visual recognition. It should be noted that the YI value can be measured by using an ultraviolet-visible-near-infrared spectrophotometer to measure the transmittance of light of 300 to 800 nm, and 3 stimulus values (X, Y, Z) are obtained, and calculated based on the formula of YI=100×(1.2769X-1.0592Z) / Y. The method for adjusting the YI value of the optical film to the above range is not particularly limited, and examples thereof include a method of using a polyimide resin as described below, a method of adding a blue pigment, a method of making the film thinner, and a method of introducing a side chain into an aromatic ring of a monomer main chain.
[0058] From the viewpoint of easily improving the folding resistance of the optical film and easily preventing wrinkles, damage, etc., the elastic modulus of the optical film of the present invention is preferably 4.8 GPa or more, more preferably 5.2 GPa or more, further preferably 6.0 GPa or more, and usually 100 GPa or less. It should be noted that the elastic modulus can be measured using a tensile testing machine (chuck distance 50 mm, tensile speed 10 mm / min), for example, by the method described in the embodiment. It should be noted that as a method for improving the elastic modulus, a method of adding a rigid inorganic filler and a method of introducing a cross-linked structure are known. However, when such a method is used, the elastic modulus is improved, and on the other hand, the improvement in yield strength is not observed in many cases. However, in the optical film of the present invention, they can be improved at the same time to achieve a further improvement in folding resistance.
[0059] The optical film of the present invention has excellent folding resistance. The optical film of the present invention preferably has a folding frequency of 80,000 or more times in the MIT folding fatigue test according to ASTM standard D2176-16, more preferably 100,000 or more times, and further preferably 250,000 or more times. If the folding frequency is above the above lower limit, the generation of cracks, ruptures, wrinkles, etc. can be effectively suppressed even if the film is repeatedly bent. It should be noted that the MIT folding fatigue test can be measured using a MIT folding fatigue tester, for example, by the method described in the examples.
[0060] The total light transmittance of the optical film of the present invention is preferably 85% or more, more preferably 88% or more, further preferably 89% or more, and particularly preferably 90% or more. If the total light transmittance is above the above lower limit, it is easy to improve visual recognition when the optical film is assembled as a front panel in a display device. The optical film of the present invention generally shows a high total light transmittance, so that, for example, compared with the case of using a film with a low transmittance, the luminous intensity of a display element required to obtain a certain brightness can be suppressed. Therefore, power consumption can be reduced. For example, when the optical film of the present invention is assembled in a display device, there is a tendency to obtain a bright display even if the amount of backlight is reduced, which can help save energy. The upper limit of the total light transmittance is generally 100% or less. It should be noted that the total light transmittance can be measured, for example, using a haze computer in accordance with JIS K 7361-1:1997. The total light transmittance can be the total light transmittance within the range of the thickness of the optical film described later. In addition, in this specification, the optical characteristics of an optical film are excellent, which means that the total light transmittance is high and / or the haze is low and / or the YI value is low, and it may be used with the same meaning as the transparency is increased or improved.
[0061] The haze of the optical film of the present invention is preferably 5% or less, more preferably 4% or less, further preferably 3% or less, further preferably 2% or less, particularly preferably 1% or less, particularly more preferably 0.8% or less, particularly more preferably 0.5% or less, and usually 0.01% or more. If the haze of the optical film is within the above range, it is easy to improve visual recognition when the optical film is assembled in a display device, especially as a front panel. It should be noted that the haze can be measured using a haze computer in accordance with JIS K7136:2000, for example, it can be measured by the method described in the examples.
[0062] The thickness of the optical film of the present invention is preferably 10 μm or more, more preferably 20 μm or more, further preferably 25 μm or more, particularly preferably 30 μm or more, preferably 200 μm or less, more preferably 100 μm or less, further preferably 80 μm or less, particularly preferably 60 μm or less, and may be a combination of these upper and lower limits. If the thickness of the optical film is within the above range, it is easy to further improve the yield strength and elastic modulus of the optical film. It should be noted that the thickness of the optical film can be measured using a micrometer, for example, by the method described in the examples.
[0063] The total light transmittance and haze vary according to the thickness of the optical film. The greater the thickness, the lower the total light transmittance and the higher the haze. That is, in a film with a large thickness, it is difficult to produce an optical film with a high total light transmittance and a low haze. In a preferred embodiment of the present invention, the optical film of the present invention has a high level of transparency, so even if the thickness is large, it can show a high total light transmittance and a low haze. Therefore, the thickness of the optical film of the present invention is preferably 10 μm or more, more preferably 15 μm or more, further preferably 20 μm or more, further preferably 25 μm or more, especially preferably 30 μm or more, especially more preferably 35 μm or more, especially more preferably 40 μm or more, preferably 100 μm or less, more preferably 80 μm or less, and more preferably 60 μm or less. The thickness of the optical film can be measured by a film thickness meter, etc., for example, it can be measured by the method described in the embodiments.
[0064] 〔Polyimide resin〕
[0065] The optical film of the present invention includes a polyimide resin. The optical film of the present invention may include one polyimide resin, or may include two or more polyimide resins. The content of the polyimide resin in the optical film of the present invention is preferably 10 parts by mass or more, more preferably 30 parts by mass or more, further preferably 50 parts by mass or more, preferably 99.5 parts by mass or less, and more preferably 95 parts by mass or less, relative to 100 parts by mass of the optical film. If the content of the polyimide resin is within the above range, it is easy to improve the yield strength, optical properties, impact resistance and elastic modulus of the optical film.
[0066] The polyimide resin contained in the optical film of the present invention may be at least one resin selected from a polyimide resin, a polyamide-imide resin and a polyamic acid resin. The polyimide resin may be one polyimide resin or two or more polyimide resins. From the viewpoint of film-forming properties and the viewpoint of easily improving yield strength, the polyimide resin is preferably a polyamide-imide resin. The polyimide resin is preferably an aromatic polyimide resin. The so-called polyimide resin is an aromatic resin, which means that preferably 60 mol% or more, more preferably 80 mol% or more, and further preferably 85 mol% or more of the structural units constituting the polyimide resin are structural units containing an aromatic structure.
[0067] In a preferred embodiment of the present invention, the polyimide resin is preferably a polyimide resin having a structural unit represented by formula (1),
[0068] [Chemical formula 5]
[0069]
[0070] [In formula (1), Y represents a tetravalent organic group, X represents a divalent organic group, and * represents a bonding end],
[0071] or a polyamide-imide resin having a structural unit represented by formula (1) and a structural unit represented by formula (3),
[0072] [Chemical formula 6]
[0073]
[0074] [In formula (3), Z and X independently represent a divalent organic group,
[0075] * indicates bonding end].
[0076] The following describes formula (1) and formula (3). The description of formula (1) relates to both polyimide resin and polyamideimide resin, and the description of formula (3) relates to polyamideimide resin.
[0077] The structural unit represented by formula (1) is a structural unit formed by the reaction of a tetracarboxylic acid compound and a diamine compound, and the structural unit represented by formula (3) is a structural unit formed by the reaction of a dicarboxylic acid compound and a diamine compound. In a preferred embodiment of the present invention in which the polyimide resin is an aromatic polyimide resin, at least one of the tetracarboxylic acid compound, the diamine compound and the dicarboxylic acid compound constituting the structural unit represented by formula (1) and the structural unit represented by formula (3) is preferably an aromatic compound (aromatic tetracarboxylic acid compound, aromatic diamine compound and / or aromatic dicarboxylic acid compound).
[0078] Y in formula (1) represents a tetravalent organic group, preferably a tetravalent organic group having 4 to 80 carbon atoms, and more preferably a tetravalent organic group having 4 to 60 carbon atoms having a cyclic structure. Examples of the cyclic structure include alicyclic rings, aromatic rings, and heterocyclic structures. The organic group is an organic group in which a hydrogen atom in the organic group may be substituted by a substituent, and examples of the substituent include a halogen atom, a monovalent hydrocarbon group having a halogen atom (e.g., an alkyl group, an aryl group, etc.), an alkoxy group, or an aryloxy group. The number of carbon atoms in the monovalent hydrocarbon group having a halogen atom, the alkoxy group, or the aryloxy group as the substituent is preferably 1 to 8. The structural unit represented by formula (1) is a repeating unit, and the polyimide resin contained in the optical film of the present invention has a plurality of structural units represented by formula (1). In the plurality of structural units represented by formula (1), Y may be the same as or different from each other. In other words, in the polyimide resin contained in the optical film of the present invention, Y in formula (1) may have one structure or two or more structures.
[0079] In a preferred embodiment of the present invention, from the viewpoint of easily improving the yield strength of the obtained optical film, the polyimide resin has a structural unit represented by formula (1), and the polyimide resin contains at least a structure (quaternary organic group) represented by formula (2) as Y in formula (1),
[0080] [Chemical formula 7]
[0081]
[0082] [In formula (2), R 1 independently represent a halogen atom, an alkyl group which may have a halogen atom, an alkoxy group, an aryl group or an aryloxy group, R 2 ~R 5 independently represent a hydrogen atom or a monovalent hydrocarbon group which may have a halogen atom, m independently represent an integer of 0 to 3, n represents an integer of 1 to 4, and * represents a bonding end, wherein in the case of R 2 ~R 5 In at least one benzene ring, R 2 ~R 5 At least one of them represents a monovalent hydrocarbon group which may have a halogen atom],
[0083] Alternatively, the polyimide resin has a structural unit represented by formula (1) and a structural unit represented by formula (3), and the polyimide resin contains at least a structure (divalent organic group) represented by formula (4") as Z in formula (3),
[0084] [Chemical formula 8]
[0085]
[0086] [In the formula (4"), W independently represents a single bond, -O-, a diphenylmethylene group, a divalent hydrocarbon group which may have a halogen atom, -SO 2 -、-S-、-CO-、-PO-、-PO 2 -、-N(R C1 )-or-Si(R C2 ) 2 -, R C1 and R C2 independently represent a hydrogen atom or an alkyl group which may have a halogen atom, R 8’
[0047] independently represent an alkyl group or an alkoxy group which may have a halogen atom, p' independently represent an integer of 1 to 4, q represents an integer of 0 to 4, and * represents a bonding end].
[0087] The present inventors have found that when a polyimide resin contains a structure represented by formula (2) as Y in formula (1); and when a polyimide resin has a structural unit represented by formula (1) and a structural unit represented by formula (3), and contains a structure represented by formula (4") as Z in formula (3), it is easy to reduce the YI of an optical film obtained using the polyimide resin and to increase the yield strength. In the above case, the polyimide resin contains a structure represented by formula (2) and / or a structure represented by formula (4"). The reason why the yield strength is easily improved when these structures are included is not clear, but the structure represented by formula (2) and the structure represented by formula (4") both have an aromatic main chain and have substituents. Such a structure is a structure that is rigid in the polyimide resin skeleton and hinders intermolecular stacking (Japanese: intermolecular packing) due to the substituents in the side chains. It is believed that by including such a structure in the polyimide resin, the polyimide resin becomes high in elastic modulus and high in toughness, and the stress until yield becomes higher. In addition, by including such a structure, the polyimide resin having a high yield strength can easily improve the transparency of the obtained optical film and easily reduce the YI value. As a result, it is possible to have both high yield strength and excellent optical properties.
[0088] R in formula (2) 1Independently represent a halogen atom, an alkyl group, an alkoxy group, an aryl group or an aryloxy group which may have a halogen atom. It should be noted that an alkyl group, an alkoxy group, an aryl group or an aryloxy group which may have a halogen atom represents an alkyl group which may have a halogen atom, an alkoxy group which may have a halogen atom, an aryl group which may have a halogen atom, or an aryloxy group which may have a halogen atom. This also applies to other similar records. As a halogen atom, for example, a fluorine atom, a chlorine atom, a bromine atom, and an iodine atom can be cited. As an alkyl group, for example, a methyl group, an ethyl group, an n-propyl group, an isopropyl group, an n-butyl group, a sec-butyl group, a tert-butyl group, an n-pentyl group, a 2-methyl-butyl group, a 3-methylbutyl group, a 2-ethyl-propyl group, a n-hexyl group, etc. can be cited. As an alkoxy group, for example, a methoxy group, an ethoxy group, a propoxy group, an isopropoxy group, a butoxy group, an isobutoxy group, a tert-butoxy group, a pentyl group, a hexyl group, a cyclohexyl group, etc. can be cited. As an aryl group, for example, a phenyl group, a tolyl group, a xylyl group, a naphthyl group, a biphenyl group, etc. can be cited. Examples of the aryloxy group include a phenoxy group, a naphthoxy group, and a biphenyloxy group. 1 Preferably, they are independently a halogen atom, an alkyl group having 1 to 6 carbon atoms which may have a halogen atom, an alkoxy group having 1 to 6 carbon atoms, an aryl group having 6 to 12 carbon atoms, or an aryloxy group having 6 to 12 carbon atoms.
[0089] In formula (2), m independently represents an integer of 0 to 3. From the viewpoint of easily improving the yield strength, elastic modulus and transparency of the optical film containing the polyimide resin, m preferably represents an integer of 0 to 2, more preferably represents 0 or 1, and even more preferably represents 0.
[0090] In formula (2), R 2 , R 3 , R 4 and R 5 Independently represent a monovalent hydrocarbon group which may have a hydrogen atom or a halogen atom. Examples of the monovalent hydrocarbon group include aromatic hydrocarbon groups, alicyclic hydrocarbon groups, and aliphatic hydrocarbon groups. Examples of aromatic hydrocarbon groups include aryl groups such as phenyl, tolyl, xylyl, naphthyl, and biphenyl. Examples of alicyclic hydrocarbon groups include cycloalkyl groups such as cyclopentyl and cyclohexyl. Examples of aliphatic hydrocarbon groups include alkyl groups such as methyl, ethyl, n-propyl, isopropyl, n-butyl, sec-butyl, tert-butyl, n-pentyl, 2-methyl-butyl, 3-methylbutyl, 2-ethyl-propyl, n-hexyl, n-heptyl, n-octyl, tert-octyl, n-nonyl, and n-decyl. Examples of halogen atoms include the halogen atoms described above. R 2 ~R 5 Preferably, they are independently a hydrogen atom, or an aryl group having 6 to 12 carbon atoms, a cycloalkyl group having 4 to 8 carbon atoms, or an alkyl group having 1 to 6 carbon atoms which may have a halogen atom. From the viewpoint of easily improving the solubility of the resin in the solvent and easily improving the yield strength, elastic modulus, and transparency of the optical film, R 2~R 5 Independently of each other, preferably, they represent a hydrogen atom or an alkyl group which may have a halogen atom, more preferably, they represent a 1-6 alkyl group which may have a hydrogen atom or a halogen atom, and still more preferably, they represent a 1-3 alkyl group which may have a hydrogen atom or a halogen atom.
[0091] In formula (2), from the viewpoint of easily improving the yield strength and optical properties of the optical film at the same time, it is preferred that 2 ~R 5 In at least one benzene ring, R 2 ~R 5 At least one of the R represents a monovalent hydrocarbon group which may have a halogen atom. In formula (2), from the viewpoint of easily improving both the yield strength and the optical properties of the optical film, 2 ~R 5 In at least one benzene ring, R 2 ~R 5 Preferably 2 to 4, more preferably 3 or 4, and still more preferably 3 of them are monovalent hydrocarbon groups which may have a halogen atom.
[0092] From the viewpoint of easily improving the solubility of the resin in the solvent and easily improving the yield strength, fracture strain, elastic modulus and transparency of the optical film, when n is 2 or more, it is more preferable to have R 2 ~R 5 In at least two benzene rings, R 2 ~R 5 At least one of them represents a monovalent hydrocarbon group which may have a halogen atom, and more preferably, at least one of them has R 2 ~R 5 Among all the benzene rings, R 2 ~R 5 At least one of them represents a monovalent hydrocarbon group which may have a halogen atom.
[0093] In formula (2), n represents an integer of 1 to 4. From the viewpoint of easily improving the elastic modulus and transparency of the optical film and easily improving the yield strength of the optical film, n is preferably an integer of 1 to 3, more preferably 2 or 3, and further preferably 2. It should be noted that the structural unit represented by formula (1) may contain one or more structures represented by formula (2) as Y.
[0094] In a preferred embodiment of the present invention, formula (2) is represented by formula (2'),
[0095] [Chemical formula 9]
[0096]
[0097] [In formula (2'), * represents a bonding end].
[0098] That is, the polyimide resin contains the structure represented by formula (2') as Y in formula (1). When the polyimide resin contains the structure represented by formula (2') as Y in formula (1), the yield strength, elastic modulus and transparency of the optical film are easily improved.
[0099] In a preferred embodiment of the present invention, in which the polyimide resin contains a structure represented by formula (2) as Y in formula (1), among the structural units represented by formula (1), the proportion of structural units in which Y in formula (1) is a structure represented by formula (2) (preferably formula (2')) is preferably 30 mol% or more, more preferably 35 mol% or more, and further preferably 40 mol% or more, and is usually 100 mol% or less, preferably 90 mol% or less, more preferably 80 mol% or less, and further preferably 70 mol% or less, relative to the total molar amount (100 mol%) of the structural units represented by formula (1). If the proportion of structural units in which Y is represented by formula (2) is above the above lower limit, it is easy to improve the yield strength and elastic modulus of the optical film. In addition, if it is below the above upper limit, it is easy to improve the fracture strain and transparency of the optical film. The proportion of structural units in which Y is represented by formula (2) can be, for example, 1 It can be measured by H-NMR or calculated from the charging ratio of the raw materials.
[0100] The polyimide resin of the present invention may have a structural unit in which Y in the formula (1) represents another tetravalent organic group in addition to or in place of the structural unit in which Y in the formula (1) is represented by the formula (2). For example, the tetravalent organic group in Y in the formula (1) includes structures represented by the formulas (20), (21), (22), (23), (24), (25), (26), (27), (28) and (29).
[0101] [Chemical formula 10]
[0102]
[0103] In formula (20) to formula (29), * represents a bonding end, W 1 represents a single bond, -O-, diphenylmethylene, a divalent hydrocarbon group which may have a halogen atom (e.g., -CH 2 -、-CH 2 -CH 2 -、-CH(CH 3 )-、-C(CH 3 ) 2 -、-C(CF 3 ) 2 -), -Ar-, -SO 2-、-S-、-CO-、-PO-、-PO 2 -、-N(R W1 )-or-Si(R W2 ) 2 -, -O-Ar-O-, -Ar-O-Ar-, -Ar-CH 2 -Ar-, -Ar-C(CH 3 ) 2 -Ar-or-Ar-SO 2 -Ar-. Ar represents an arylene group having 6 to 20 carbon atoms which may have a fluorine atom, and a specific example thereof is a phenylene group. W1 and R W2 Each of them independently represents a hydrogen atom or an alkyl group which may have a halogen atom. It should be noted that the hydrogen atoms on the ring in formulas (20) to (29) may be substituted by an alkyl group having 1 to 6 carbon atoms, an alkoxy group having 1 to 6 carbon atoms, or an aryl group having 6 to 12 carbon atoms. Examples of the alkyl group having 1 to 6 carbon atoms, the alkoxy group having 1 to 6 carbon atoms, and the aryl group having 6 to 12 carbon atoms include R 1 The groups exemplified above.
[0104] Among the groups represented by formula (20) to formula (29), from the viewpoint of easily improving the yield strength, fracture strain, elastic modulus and transparency of the optical film, the group represented by formula (26), formula (28) or formula (29) is preferred, and the group represented by formula (26) is more preferred. In addition, from the viewpoint of easily improving the yield strength, fracture strain, elastic modulus and transparency of the optical film, W 1 Preferably, it represents a single bond, -O-, -CH 2 -、-CH 2 -CH 2 -、-CH(CH 3 )-、-C(CH 3 ) 2 -or-C(CF 3 ) 2 -, more preferably represents a single bond, -O-, -CH 2 -、-CH(CH 3 )-、-C(CH 3 ) 2 -or-C(CF 3 ) 2 -, more preferably represents a single bond, -C(CH 3 ) 2 -or-C(CF 3 ) 2 -, further preferably represents a single bond or -C(CF 3 ) 2 -, particularly preferably -C(CF3 ) 2 In the above-mentioned preferred embodiment in which the polyimide resin contains the structure represented by formula (2) as Y in formula (1), from the viewpoint of easily further improving the yield strength of the optical film, the polyimide resin preferably has a structural unit represented by formula (26) in addition to a structural unit represented by formula (2) in which Y in formula (1).
[0105] In a preferred embodiment of the present invention, formula (26) is preferably represented by formula (5),
[0106] [Chemical formula 11]
[0107]
[0108] [In formula (5), B represents a single bond, -O-, a diphenylmethylene group, a divalent hydrocarbon group which may have a halogen atom, -SO 2 -, -S-, -CO-, -COO-, -PO-, -PO 2 -、-N(R B1 )-or-Si(R B2 ) 2 -, R B1 and R B2 independently represent a hydrogen atom or an alkyl group which may have a halogen atom, R 7
[0063] independently represent a halogen atom, an alkyl group which may have a halogen atom, an alkoxy group, an aryl group or an aryloxy group, independently represent an integer of 0 to 3, and * represents a bonding end].
[0109] When the polyimide resin has a structural unit in which Y in formula (1) is represented by formula (5) in addition to a structural unit in which Y in formula (1) is represented by formula (2), the solubility of the resin in a solvent and the yield strength and transparency of the optical film are easily improved.
[0110] R in formula (5) 7 and R are independently a halogen atom, an alkyl group which may have a halogen atom, an alkoxy group, an aryl group or an aryloxy group. Examples of the halogen atom, the alkyl group which may have a halogen atom, the alkoxy group, the aryl group and the aryloxy group include: 1 From the viewpoint of improving the yield strength, fracture strain, elastic modulus and transparency of the optical film, R 7 Independently of each other, preferably, they represent an alkyl group having 1 to 6 carbon atoms which may have a halogen atom, and more preferably, they represent an alkyl group having 1 to 3 carbon atoms which may have a halogen atom.
[0111] In formula (5), t independently represents an integer of 0 to 3, and is preferably an integer of 0 to 2, more preferably 0 or 1, and even more preferably 0, from the viewpoint of easily improving the yield strength, breaking strain, elastic modulus and transparency of the optical film.
[0112] In formula (5), B represents a single bond, -O-, a diphenylmethylene group, a divalent hydrocarbon group which may have a halogen atom, -SO 2 -, -S-, -CO-, -COO-, -PO-, -PO 2 -、-N(R B1 )-or-Si(R B2 ) 2 -, R B1 and R B2 Each independently represents a hydrogen atom or an alkyl group which may have a halogen atom.
[0113] Examples of the divalent hydrocarbon group which may have a halogen atom include: 2 ~R 5 A divalent group obtained by replacing one hydrogen atom in a monovalent hydrocarbon group which may have a halogen atom. For a divalent hydrocarbon group which may have a halogen atom, two hydrogen atoms in the hydrogen atoms contained in the group may be substituted to form a ring, that is, the two hydrogen atoms may be substituted as bonding ends and the two bonding ends may be connected to form a ring. Examples of the ring include a cycloalkane ring having 3 to 12 carbon atoms. In addition, as -N(R) contained in B in formula (5), B1 )- and -Si(R B2 ) 2 -R in B1 and R B2 The alkyl group which may be substituted by a halogen atom in the formula (3) may be exemplified as R 1 The alkyl group which may have a halogen atom is the group exemplified above.
[0114] From the viewpoint of easily improving the yield strength, breaking strain, elastic modulus and transparency of the optical film, B in formula (5) preferably represents a single bond or a divalent hydrocarbon group which may have a halogen atom, and more preferably represents a single bond, -CH 2 -、-CH 2 -CH 2 -、-CH(CH 3 )-、-C(CH 3 ) 2 -or-C(CF 3 ) 2 -, more preferably represents a single bond, -C(CH 3 ) 2 -or-C(CF 3 ) 2-, further preferably represents a single bond or -C(CF 3 ) 2 -, particularly preferably -C(CF 3 ) 2 -.
[0115] In a preferred embodiment of the present invention, formula (5) is represented by formula (5').
[0116] [Chemical formula 12]
[0117]
[0118] [In formula (5'), * represents a bonding end].
[0119] That is, the polyimide resin preferably has a structural unit represented by formula (5') as at least a part of the structural unit represented by formula (1). In this case, the yield strength, transparency, elastic modulus and bending resistance of the optical film are easily improved.
[0120] In the case where the polyimide resin contains a structural unit in which Y in formula (1) is represented by formula (5), among the structural units represented by formula (1), the proportion of the structural unit in which Y in formula (1) is a structure represented by formula (5), preferably represented by formula (5'), relative to the total molar amount (100 mol%) of the structural units represented by formula (1), is preferably 30 mol% or more, more preferably 35 mol% or more, further preferably 40 mol% or more, preferably 90 mol% or less, more preferably 80 mol% or less, further preferably 70 mol% or less. If the proportion of the structural unit in which Y is represented by formula (5) is above the above lower limit, it is easy to improve the solubility of the resin in the solvent and the transparency of the optical film. In addition, if it is below the above upper limit, it is easy to improve the yield strength and elastic modulus of the optical film. It should be noted that the proportion of the structural unit in which Y in formula (1) is represented by formula (5) can be, for example, 1 It can be measured by H-NMR or calculated from the charging ratio of the raw materials.
[0121] In one embodiment of the present invention, when the polyimide resin contains a structural unit in which Y in formula (1) is represented by formula (2) and a structural unit in which Y in formula (1) is represented by formula (5), the total ratio of the structural unit represented by formula (2) and the structural unit represented by formula (5) relative to the total molar amount of the structural unit represented by formula (1) is preferably 50 mol% or more, more preferably 70 mol% or more, further preferably 90 mol% or more, and usually 100 mol% or less. If the total ratio is within the above range, it is easy to improve the yield strength, fracture strain, elastic modulus and transparency of the optical film. It should be noted that the total ratio can be, for example, 1It can be measured by H-NMR or calculated from the charging ratio of the raw materials.
[0122] X in formula (1) represents a divalent organic group, preferably a divalent organic group having 4 to 40 carbon atoms. From the viewpoint of easily improving the yield strength, fracture strain, elastic modulus and transparency of the optical film, the polyimide resin of the present invention preferably contains at least one of a divalent aromatic group, a divalent alicyclic group and a divalent aliphatic group as X in formula (1), and more preferably contains a divalent aromatic group as X in formula (1). Examples of the divalent aromatic group include R in formula (2): 2 ~R 5 One of the hydrogen atoms in the monovalent aromatic hydrocarbon group exemplified above is replaced by a divalent aromatic hydrocarbon group at the bonding end; at least one of the divalent aromatic hydrocarbon groups is connected to the divalent aromatic hydrocarbon group by a linking group, such as V described below. 1 Examples of the divalent alicyclic group include R 2 ~R 5 One of the hydrogen atoms in the monovalent alicyclic hydrocarbon group exemplified above is replaced by a divalent alicyclic hydrocarbon group at the bonding end; at least one of the divalent alicyclic hydrocarbon groups is connected to the bond end by a linking group, such as V described below. 1 Examples of the divalent aliphatic group include R 2 ~R 5 One of the hydrogen atoms in the monovalent aliphatic hydrocarbon group exemplified above is replaced by a divalent aliphatic hydrocarbon group at the bonding end; at least one of the divalent aliphatic hydrocarbon groups is connected to the divalent aliphatic hydrocarbon group by a linking group, such as V described below. 1 A group formed by bonding of other connecting groups.
[0123] In formula (1), X preferably represents a divalent organic group having 4 to 40 carbon atoms and having a cyclic structure (alicyclic, aromatic, heterocyclic, etc.), more preferably represents a divalent aromatic group having 4 to 40 carbon atoms and a divalent alicyclic group having 4 to 40 carbon atoms, and further preferably represents a divalent aromatic group having 4 to 40 carbon atoms. In the organic group, the hydrogen atoms in the organic group may be substituted by a hydrocarbon group or a fluorine-substituted hydrocarbon group. In this case, the hydrocarbon group and the fluorine-substituted hydrocarbon group preferably have 1 to 8 carbon atoms. In one embodiment of the present invention, the polyamide-imide resin of the present invention may contain a plurality of Xs, and the plurality of Xs may be the same or different from each other. Examples of X include groups represented by formula (10), formula (11), formula (12), formula (13), formula (14), formula (15), formula (16), formula (17) and formula (18); groups in which the hydrogen atoms in the groups represented by formula (10) to formula (18) are substituted by methyl, fluoro, chloro or trifluoromethyl groups. It should be noted that the hydrogen atoms on the rings in formulas (10) to (18) may be substituted by an alkyl group having 1 to 6 carbon atoms, an alkoxy group having 1 to 6 carbon atoms, or an aryl group having 6 to 12 carbon atoms. Examples of the alkyl group having 1 to 6 carbon atoms, the alkoxy group having 1 to 6 carbon atoms, and the aryl group having 6 to 12 carbon atoms include R 1 The groups exemplified above.
[0124] [Chemical formula 13]
[0125]
[0126] In formula (10) to formula (18), * represents a bonding end, V 1 、V 2 and V 3 Independently represent a single bond, -O-, -S-, -CH 2 -、-CH 2 -CH 2 -、-CH(CH 3 )-、-C(CH 3 ) 2 -、-C(CF 3 ) 2 -、-SO 2 -, -CO- or -N(Q)-. Here, Q represents a monovalent hydrocarbon group having 1 to 12 carbon atoms which may have a halogen atom.
[0127] Examples of the monovalent hydrocarbon group having 1 to 12 carbon atoms which may have a halogen atom include: 2 ~R 5 The monovalent hydrocarbon group which may have a halogen atom is the group exemplified above.
[0128] As an example, V 1 and V 3 is a single bond, -O- or -S-, and V 2 -CH 2 -、-C(CH 3 ) 2 -、-C(CF 3 ) 2 -or-SO 2 -. V 1 and V 2 The bonding position relative to each ring, and V 2 and V 3 The bonding position to each ring is preferably the meta position or the para position, and more preferably the para position, independently of each other with respect to each ring.
[0129] In a preferred embodiment of the present invention, the polyimide resin of the present invention may include a structure represented by formula (6) as X in formula (1),
[0130] [Chemical formula 14]
[0131]
[0132] [In formula (6), A represents a single bond, -O-, a diphenylmethylene group, a divalent hydrocarbon group which may have a halogen atom, -SO 2 -、-S-、-CO-、-PO-、-PO 2 -、-N(R A1 )-or-Si(R A2 ) 2 -, R A1 and R A2 independently represent a hydrogen atom or an alkyl group which may have a halogen atom, R 6
[0047] independently represent a halogen atom, an alkyl group which may have a halogen atom, an alkoxy group, an aryl group or an aryloxy group, independently represent an integer of 0 to 4, and * represents a bonding end].
[0133] In the case where the polyimide resin has a structural unit in which X in formula (1) is represented by formula (6), it is easy to improve the yield strength, fracture strain, elastic modulus and transparency of the optical film. In the present invention, the polyimide resin may contain one or more groups represented by formula (6) as X in the structural unit represented by formula (1).
[0134] R in formula (6) 6 and R are independently a halogen atom, an alkyl group which may have a halogen atom, an alkoxy group, an aryl group or an aryloxy group. Examples of the halogen atom, the alkyl group which may have a halogen atom, the alkoxy group, the aryl group and the aryloxy group include: 1 The groups exemplified above.
[0135] Among them, from the viewpoint of easily improving the yield strength, fracture strain, elastic modulus and transparency of the optical film, R 6 Preferably, they are independently an alkyl group having 1 to 6 carbon atoms or a halogenated alkyl group having 1 to 6 carbon atoms, and more preferably an alkyl group having 1 to 6 carbon atoms or a fluoroalkyl group having 1 to 6 carbon atoms (preferably a perfluoroalkyl group). 6 Each of the s independently represents a methyl group, a chloro group or a trifluoromethyl group. Each of the s independently represents an integer of 0 to 4. From the viewpoint of easily improving the yield strength, the breaking strain, the elastic modulus and the transparency of the optical film, it is preferably an integer of 1 to 3, more preferably 1 or 2, and still more preferably 1. In a preferred embodiment of the present invention, it is preferred that in each benzene ring, s is 1, and R is substituted at the ortho position based on -A-. 6 , and R 6 It is methyl, fluoro, chloro or trifluoromethyl.
[0136] In formula (6), the positions of the bonding ends are preferably meta or para, more preferably para, independently of each other based on -A-, from the viewpoint of easily improving the yield strength, breaking strain, elastic modulus and transparency of the optical film.
[0137] In formula (6), A represents a single bond, -O-, a diphenylmethylene group, a divalent hydrocarbon group which may have a halogen atom, -SO 2 -、-S-、-CO-、-PO-、-PO 2 -、-N(R A1 )-or-Si(R A2 ) 2 -, R A1 and R A2 Each independently represents a hydrogen atom or an alkyl group which may have a halogen atom.
[0138] Examples of the divalent hydrocarbon group which may have a halogen atom include: 2 ~R 5 A divalent group obtained by replacing one hydrogen atom in a monovalent hydrocarbon group which may have a halogen atom. For a divalent hydrocarbon group which may have a halogen atom, two hydrogen atoms in the group may be substituted to form a ring, that is, the two hydrogen atoms may be substituted as bonding ends and the two bonding ends may be connected to form a ring. Examples of the ring include a cycloalkane ring having 3 to 12 carbon atoms. In addition, as -N(R) contained in A in formula (4), A1 )- and -Si(R A2 ) 2 -R A1 and R A2 The alkyl group which may have a halogen atom in the formula (3) may be1 The alkyl group which may have a halogen atom is the group exemplified above.
[0139] From the viewpoint of easily improving the yield strength, breaking strain, elastic modulus and transparency of the optical film, A in formula (6) preferably represents a single bond, -CH 2 -、-CH 2 -CH 2 -、-CH(CH 3 )-、-C(CH 3 ) 2 -or-C(CF 3 ) 2 -, more preferably represents a single bond, -C(CH 3 ) 2 -or-C(CF 3 ) 2 -, further preferably represents a single bond or -C(CF 3 ) 2 -, particularly preferably represents a single bond.
[0140] In a preferred embodiment of the present invention, from the viewpoint of easily improving the fracture strain, elastic modulus and transparency of the optical film and easily improving the yield strength of the optical film, in formula (6), R 6 each independently represents a halogenated alkyl group having 1 to 6 carbon atoms, s represents 1 or 2, A represents a single bond, -C(CH 3 ) 2 -or-C(CF 3 ) 2 -.
[0141] In a preferred embodiment of the present invention, formula (6) is represented by formula (6'),
[0142] [Chemical formula 15]
[0143]
[0144] That is, it is preferred that at least a part of the plurality of Xs in formula (1) is represented by formula (6'). In such a form, the yield strength, breaking strain, elastic modulus, and transparency of the optical film are easily improved.
[0145] Among the structural units represented by formula (1), the proportion of the structural units in which X in formula (1) is a structure represented by formula (6) is preferably 50 mol% or more, more preferably 70 mol% or more, further preferably 80 mol% or more, and usually 100 mol% or less, relative to the total molar amount (100 mol%) of the structural units represented by formula (1). If the proportion of the structural units in which X is represented by formula (4) is above the above lower limit, it is easy to further improve the transparency of the optical film. In addition, if it is below the above upper limit, it is easy to further improve the yield strength of the optical film. It should be noted that the proportion of the structural units in which X in formula (1) is represented by formula (6), for example, can be used 1 It can be measured by H-NMR or calculated from the charging ratio of the raw materials.
[0146] As described above, the polyimide resin contained in the optical film of the present invention may have a structural unit represented by formula (3) in addition to the structural unit represented by formula (1).
[0147] [Chemical formula 16]
[0148]
[0149] When the polyimide resin has the structural unit represented by formula (3), the resin is also referred to as a polyamide-imide resin.
[0150] Z in formula (3) represents a divalent organic group, preferably a divalent organic group having 4 to 40 carbon atoms which may have a hydrocarbon group having 1 to 8 carbon atoms or a hydrocarbon group having 1 to 8 carbon atoms substituted by fluorine, and more preferably a divalent organic group having 4 to 40 carbon atoms which may have a hydrocarbon group having 1 to 8 carbon atoms or a hydrocarbon group having 1 to 8 carbon atoms substituted by fluorine. Examples of the cyclic structure include alicyclic, aromatic and heterocyclic structures. Examples of the divalent organic group having an alicyclic and aromatic ring include groups in which two non-adjacent bonding ends of the groups represented by formula (20), (21), (22), (23), (24), (25), (26), (27), (28) and (29) are replaced by hydrogen atoms, and divalent chain hydrocarbon groups having 6 or less carbon atoms.
[0151] [Chemical formula 17]
[0152]
[0153] [In formula (20) to formula (29),
[0154] W 1 represents a single bond, -O-, diphenylmethylene, a divalent hydrocarbon group which may have a halogen atom (e.g., -CH 2 -、-CH 2-CH 2 -、-CH(CH 3 )-、-C(CH 3 ) 2 -、-C(CF 3 ) 2 -), -Ar-, -SO 2 -、-S-、-CO-、-PO-、-PO 2 -、-N(R W1 )-or-Si(R W2 ) 2 -, -O-Ar-O-, -Ar-O-Ar-, -Ar-CH 2 -Ar-, -Ar-C(CH 3 ) 2 -Ar-or-Ar-SO 2 -Ar-, wherein Ar independently represents an arylene group having 6 to 20 carbon atoms (e.g., phenylene group) which may have a fluorine atom, and R W1 and R W2
[0063] independently represent a hydrogen atom or an alkyl group which may have a halogen atom, and * represents a bonding end].
[0155] As the divalent organic group having a heterocyclic structure, a group having a thiophene ring skeleton can be cited. From the viewpoint of easily reducing the YI value of the optical film, a group in which two non-adjacent bonding ends of the groups represented by formulae (20) to (29) are replaced with hydrogen atoms and a group having a thiophene ring skeleton are preferred.
[0156] As Z in formula (3), more preferably, a divalent organic group represented by formula (20'), formula (21'), formula (22'), formula (23'), formula (24'), formula (25'), formula (26'), formula (27'), formula (28') and formula (29') is
[0157] [Chemical formula 18]
[0158]
[0159] [In formula (20') to formula (29'), W 1 and * as defined in formula (20) to formula (29)]
[0160] It should be noted that the hydrogen atoms on the rings of formulas (20) to (29) and (20') to (29') may be substituted by an alkyl group having 1 to 6 carbon atoms, an alkoxy group having 1 to 6 carbon atoms, or an aryl group having 6 to 12 carbon atoms. Examples of the alkyl group having 1 to 6 carbon atoms, the alkoxy group having 1 to 6 carbon atoms, and the aryl group having 6 to 12 carbon atoms include R 1 The groups exemplified above.
[0161] In a preferred embodiment of the present invention, the polyimide-based resin contained in the optical film of the present invention may include a structure represented by formula (4) as Z in formula (3).
[0162] [Chemical formula 19]
[0163]
[0164] [In formula (4), W independently represents a single bond, -O-, a diphenylmethylene group, a divalent hydrocarbon group which may have a halogen atom, -SO 2 -、-S-、-CO-、-PO-、-PO 2 -、-N(R C1 )-or-Si(R C2 ) 2 -, R C1 and R C2 independently represent a hydrogen atom or an alkyl group which may have a halogen atom, R 8 [a] independently represent a halogen atom, an alkyl group which may have a halogen atom, an alkoxy group, an aryl group or an aryloxy group, p independently represent an integer of 0 to 4, q represents an integer of 0 to 4, and * represents a bonding end]
[0165] When the polyimide resin has a structural unit represented by formula (3) in which Z is represented by formula (4), the yield strength, fracture strain, elastic modulus and transparency of the optical film can be easily improved. It should be noted that the structural unit represented by formula (3) may contain one or more groups represented by formula (4) as Z.
[0166] In formula (3), the bonding position of W is preferably the meta position or the para position, and more preferably the para position, independently of the bonding end, from the viewpoint of easily improving the yield strength, fracture strain, elastic modulus and transparency of the optical film.
[0167] In a preferred embodiment of the present invention, formula (4) is represented by formula (4'),
[0168] [Chemical formula 20]
[0169]
[0170] [In formula (4'), W, R 8 , p and q are as defined in formula (4)].
[0171] In other words, in at least a part of the structural units represented by formula (3) contained in the polyimide resin as appropriate, Z in formula (3) is preferably represented by formula (4'). In this case, the yield strength, breaking strain, elastic modulus and transparency of the optical film are easily improved.
[0172] In formula (4) and formula (4'), R 8 and R in formula (2) are independently a halogen atom, an alkyl group which may have a halogen atom, an alkoxy group, an aryl group or an aryloxy group. 1 The groups exemplified above.
[0173] Among them, from the viewpoint of easily improving the yield strength, fracture strain, elastic modulus and transparency of the optical film, R 8 Preferably, they are independently an alkyl group having 1 to 6 carbon atoms or an alkoxy group having 1 to 6 carbon atoms which may have a halogen atom, and more preferably an alkyl group having 1 to 3 carbon atoms or an alkoxy group having 1 to 3 carbon atoms. p is independently an integer of 0 to 4, and is preferably an integer of 0 to 2 from the viewpoint of easily improving the yield strength, breaking strain, elastic modulus and transparency of the optical film.
[0174] W in formula (4) and formula (4') independently represents a single bond, -O-, a diphenylmethylene group, a divalent hydrocarbon group which may have a halogen atom, -SO 2 -、-S-、-CO-、-PO-、-PO 2 -、-N(R C1 )-or-Si(R C2 ) 2 -, from the viewpoint of easily improving the yield strength, breaking strain, elastic modulus and transparency of the optical film, preferably represents -O- or -S-, and more preferably represents -O-. C1 and R C2 and independently represent a hydrogen atom or a monovalent hydrocarbon group having 1 to 12 carbon atoms which may have a halogen atom. Examples of the monovalent hydrocarbon group having 1 to 12 carbon atoms which may have a halogen atom include: 2 ~R 5 The monovalent hydrocarbon group which may have a halogen atom is the group exemplified above.
[0175] In formula (4) and formula (4'), q is an integer in the range of 0 to 4. If q is within this range, the yield strength, fracture strain, elastic modulus and transparency of the optical film are easily improved. In formula (4) and formula (4'), q is preferably an integer in the range of 0 to 3, and more preferably an integer in the range of 0 to 2.
[0176] The structural unit represented by formula (4) or formula (4') in which q is 0 is, for example, a structural unit derived from terephthalic acid or isophthalic acid. The structural unit is preferably a structural unit in which p and q in formula (4) or formula (4') are respectively 0 or q is 0 and p is 1 or 2 (preferably R 8The polyamide-imide resin preferably contains a structural unit derived from terephthalic acid from the viewpoint of easily improving the yield strength, fracture strain, elastic modulus and transparency of the optical film. The polyamide-imide resin may contain one or more structural units represented by formula (4) or formula (4') in Z.
[0177] In one embodiment of the present invention, as Z in formula (3), in the case of containing the structure represented by formula (4), in the structural unit represented by formula (3), the proportion of the structural unit represented by formula (4) in which X is preferably 30 mol% or more, more preferably 50 mol% or more, further preferably 70 mol% or more, and usually 100 mol% or less relative to the total molar amount of the structural unit represented by formula (3). If the proportion of the structural unit represented by formula (4) in which Z in formula (3) is greater than the above lower limit, it is easy to improve the fracture strain, elastic modulus and transparency of the optical film, and it is easy to improve the yield strength of the optical film. If the proportion is below the above upper limit, it is easy to suppress the increase in viscosity of the resin varnish caused by the hydrogen bonds between the amide bonds of formula (4), and it is easy to improve the processability of the film. It should be noted that the proportion of the structural unit represented by formula (4) in which Z in formula (3) is, for example, 1 The above description of the preferred ratio also applies to the structure represented by formula (4') and the structure represented by formula (4").
[0178] In one embodiment of the present invention, when the polyimide resin contains a structure represented by formula (4) as Z in formula (3), in the structural unit represented by formula (3), the proportion of the structural unit in which X is represented by formula (4) relative to the total molar amount of the structural unit represented by formula (1) and the structural unit represented by formula (3) is preferably 5 mol% or more, more preferably 15 mol% or more, further preferably 30 mol% or more, particularly preferably 50 mol% or more, and usually 100 mol% or less. If the proportion of the structural unit in which Z in formula (3) is represented by formula (4) is above the above lower limit, it is easy to improve the yield strength, fracture strain, elastic modulus and transparency of the optical film. If the proportion is below the above upper limit, it is easy to suppress the increase in viscosity of the resin varnish caused by hydrogen bonds between amide bonds of formula (4), and it is easy to improve the processability of the film. It should be noted that the proportion of the structural unit in which Z in formula (3) is represented by formula (4) can be used, for example 1 The above description of the preferred ratio also applies to the structure represented by formula (4') and the structure represented by formula (4").
[0179] In the case where the polyamide-imide resin has a structural unit in which Z in formula (3) is represented by any one of the above-mentioned formulas (20') to (29'), and in the case where the polyamide-imide resin has a structural unit in which Z in formula (3) is represented by formula (4'), from the viewpoint of suppressing the increase in viscosity of the resin varnish due to hydrogen bonding between amide bonds and film processability, it is preferred that the polyamide-imide resin has a structural unit derived from carboxylic acid represented by formula (d1) in addition to the structural units represented by formula (1) and formula (3).
[0180] [Chemical formula 21]
[0181]
[0182] [In formula (d1), R 24 are independently a hydrogen atom, an alkyl group having 1 to 6 carbon atoms, an alkoxy group having 1 to 6 carbon atoms, or an aryl group having 6 to 12 carbon atoms, and R 25 Represents R 24 or -C(=O)-, *denotes a bonding end].
[0183] R 24 In the formula (2), the alkyl group having 1 to 6 carbon atoms, the alkoxy group having 1 to 6 carbon atoms, and the aryl group having 6 to 12 carbon atoms include: 1 As the structural unit (d1), specifically, R 24 and R 25 All of them are hydrogen atoms (structural units derived from dicarboxylic acid compounds), R 24 are all hydrogen atoms, and R 25 It represents a structural unit of -C(=O)-* (a structural unit derived from a tricarboxylic acid compound) and the like.
[0184] In the case where the polyamide-imide resin contains a structural unit represented by formula (d1), the proportion of the structural unit represented by formula (d1) relative to the total molar amount of the structural unit represented by formula (1) and the structural unit represented by formula (3) is preferably 0.01 mol% or more, more preferably 0.1 mol% or more, further preferably 1 mol% or more, preferably 30 mol% or less, more preferably 20 mol% or less, further preferably 10 mol% or less. If the ratio is within the above range, it is easy to suppress the increase in viscosity of the resin varnish caused by hydrogen bonds between amide bonds, and it is easy to improve the processability of the film. It should be noted that this ratio can be used, for example 1 It can be measured by H-NMR or calculated from the charging ratio of the raw materials.
[0185] In a preferred embodiment of the present invention, the polyimide resin contained in the optical film of the present invention has a structural unit represented by formula (1) and a structural unit represented by formula (3), and as Z in formula (3), it contains at least a structure represented by formula (4"),
[0186] [Chemical formula 22]
[0187]
[0188] [In the formula (4"), W independently represents a single bond, -O-, a diphenylmethylene group, a divalent hydrocarbon group which may have a halogen atom, -SO 2 -、-S-、-CO-、-PO-、-PO 2 -、-N(R C1 )-or-Si(R C2 ) 2 -, R C1 and R C2 independently represent a hydrogen atom or an alkyl group which may have a halogen atom, R 8’
[0063] independently represent an alkoxy group which may have a halogen atom, p' independently represent an integer of 1 to 4, q represents an integer of 0 to 4, and * represents a bonding end].
[0189] When the polyimide resin includes the structure represented by the above formula (4"), the yield strength of the polyimide resin can be easily increased. In addition, the optical properties of the obtained optical film can be easily improved.
[0190] Regarding W and q in formula (4"), the same description as that related to W and q in the above formula (4) applies. R in formula (4") 8’ Each of the p's independently represents an integer of 1 to 4, preferably an integer of 1 to 2. Each of the p's independently represents an integer of 1 to 4, preferably an integer of 1 to 2.
[0191] As X in formula (3), the groups exemplified above as X in formula (1) can be cited, and the preferred modes are also the same. In addition, X in formula (1) and X in formula (3) may be the same or different. In one embodiment of the present invention, the structural unit represented by formula (1) and / or the structural unit represented by formula (3) may include one or more structures (or groups) represented by formula (5) as X.
[0192] In one embodiment of the present invention, when X in formula (1) and formula (3) includes a structure represented by formula (5), the proportion of the structural unit represented by formula (5) relative to the total molar amount of the structural unit represented by formula (1) and the structural unit represented by formula (3) is preferably 30 mol% or more, more preferably 50 mol% or more, further preferably 70 mol% or more, and usually 100 mol% or less. If the proportion of the structural unit represented by formula (5) is within the above range, it is easy to improve the yield strength, fracture strain, elastic modulus and transparency of the optical film. It should be noted that the proportion of the structural unit represented by formula (5) can be, for example, 1 It can be measured by H-NMR or calculated from the charging ratio of the raw materials.
[0193] The polyimide resin of the present invention may contain a structural unit represented by formula (30) and / or a structural unit represented by formula (31) in addition to the structural unit represented by formula (1) and, if necessary, the structural unit represented by formula (3).
[0194] [Chemical formula 23]
[0195]
[0196] In formula (30), Y 1 is a tetravalent organic group, preferably an organic group in which the hydrogen atoms in the organic group may be substituted by a hydrocarbon group or a fluorine-substituted hydrocarbon group. 1 , groups represented by formula (20), formula (21), formula (22), formula (23), formula (24), formula (25), formula (26), formula (27), formula (28) and formula (29), groups in which hydrogen atoms in the groups represented by formula (20) to formula (29) are replaced by methyl, fluoro, chloro or trifluoromethyl, and tetravalent chain hydrocarbon groups having 6 or less carbon atoms. In one embodiment of the present invention, the structural unit represented by formula (30) may contain multiple Y 1 The structure shown, various Y 1 They can be the same or different from each other.
[0197] In formula (31), Y 2 is a trivalent organic group, preferably an organic group in which the hydrogen atoms in the organic group may be substituted by a hydrocarbon group or a fluorine-substituted hydrocarbon group. 2 , a group obtained by replacing any one of the bonding ends of the groups represented by the above-mentioned formula (20), formula (21), formula (22), formula (23), formula (24), formula (25), formula (26), formula (27), formula (28) and formula (29) with a hydrogen atom, and a trivalent chain hydrocarbon group having 6 or less carbon atoms. In one embodiment of the present invention, the structural unit represented by formula (31) may contain multiple Y2 The structure shown, various Y 2 They can be the same or different from each other.
[0198] In formula (30) and formula (31), X 1 and X 2 Each of X is independently a divalent organic group, and preferably an organic group in which the hydrogen atom in the organic group may be substituted by a hydrocarbon group or a fluorine-substituted hydrocarbon group. 1 and X 2 Examples include the groups represented by the above-mentioned formula (10), formula (11), formula (12), formula (13), formula (14), formula (15), formula (16), formula (17) and formula (18); groups obtained by replacing the hydrogen atoms in the groups represented by formula (10) to formula (18) with methyl, fluoro, chloro or trifluoromethyl groups; and chain hydrocarbon groups having less than 6 carbon atoms.
[0199] In the case where the polyimide resin contains a structural unit represented by formula (30) and / or a structural unit represented by formula (31), the total ratio of the structural unit represented by formula (30) and the structural unit represented by formula (31) relative to the total molar amount of the structural unit represented by formula (1) and the structural unit represented by formula (3) is preferably 0.01 mol% or more, more preferably 0.1 mol% or more, further preferably 1 mol% or more, preferably 30 mol% or less, more preferably 20 mol% or less, further preferably 10 mol% or less. If the total ratio is within the above range, an optical film with a high elastic modulus can be easily obtained. It should be noted that this ratio can be used, for example 1 It can be measured by H-NMR or calculated from the charging ratio of the raw materials.
[0200] In the case where the polyimide resin has a structural unit represented by formula (1) and a structural unit represented by formula (3), the proportion of the structural unit represented by formula (1) relative to the total molar amount (100 mol%) of the structural unit represented by formula (1) and the structural unit represented by formula (3) is preferably 10 mol% or more, more preferably 15 mol% or more, further preferably 20 mol% or more, particularly preferably 25 mol% or more, preferably 90 mol% or less, more preferably 70 mol% or less, further preferably 60 mol% or less, and particularly preferably 50 mol% or less. In the polyamideimide resin, if the proportion of the structural unit represented by formula (1) is above the above lower limit, the viscosity increase caused by the hydrogen bonds between the amide bonds in formula (2) can be suppressed, the viscosity of the polyamideimide varnish can be reduced, and the manufacture of optical components is easy. In the polyamideimide resin, if the proportion of the structural unit represented by formula (1) is below the above upper limit, the optical film formed by containing the polyamideimide resin exhibits high surface hardness. It should be noted that the above proportion can be, for example, 1It can be measured by H-NMR or calculated from the charging ratio of the raw materials.
[0201] The weight average molecular weight (hereinafter, sometimes referred to as Mw) of the polyimide resin contained in the optical film of the present invention is preferably 100,000 or more, more preferably 150,000 or more, further preferably 200,000 or more, further preferably 300,000 or more, particularly further preferably 400,000 or more, particularly more preferably 500,000 or more, particularly further preferably 600,000 or more, preferably 1,500,000 or less, more preferably 1,200,000 or less, further preferably 1,000,000 or less, particularly preferably 800,000 or less. If the Mw of the polyimide resin is above the lower limit, the yield strength, fracture strain and elastic modulus of the obtained optical film are easily improved. In addition, if the Mw is below the upper limit, the gelation of the resin varnish is easily suppressed, and the optical properties of the obtained optical film are easily improved. Here, when the polyimide resin of the present invention comprises the structure shown in formula (2) as Y in formula (1), it is known that the viscosity of the solution of the polyimide resin with this structure has a trend of increasing. The Mw of the polyimide resin increases, and there is also a trend of increasing the viscosity of the resin solution. Therefore, it is very difficult to high-molecular-weight the polyimide resin comprising such a structure. The inventor has carried out various studies, and it was found that by manufacturing the polyimide resin under the manufacturing conditions described later, Mw can be improved. Mw can, for example, be measured by gel permeation chromatography (hereinafter, sometimes described as GPC), converted by standard polystyrene, and obtained, for example, can be obtained by the method described in the embodiment.
[0202] In a preferred embodiment of the present invention, the polyimide resin in the present invention may contain halogen atoms such as fluorine atoms that can be introduced through the above-mentioned fluorine-containing substituents. When the polyimide resin contains halogen atoms, it is easy to reduce the YI value of the optical film, and it is easy to increase the fracture strain and elastic modulus. If the elastic modulus of the optical film is high, it is easy to suppress the generation of damage and wrinkles. In addition, if the YI value of the optical film is low, it is easy to improve the transparency and visual recognition of the film. The halogen atom is preferably a fluorine atom. As a preferred fluorine-containing substituent in order to make the polyimide resin contain fluorine atoms, for example, a fluoro group and a trifluoromethyl group can be cited.
[0203] When the polyimide resin contains halogen atoms, the content thereof is preferably 1 to 40% by mass, more preferably 5 to 40% by mass, and further preferably 5 to 30% by mass, based on the mass of the polyimide resin. If the content of halogen atoms is above the above lower limit, the YI value of the optical film is easily reduced, and the fracture strain and elastic modulus are easily increased. If the content of halogen atoms is below the above upper limit, synthesis becomes easy.
[0204] The imidization rate of the polyimide resin is preferably 90% or more, more preferably 93% or more, and further preferably 96% or more. From the viewpoint of easily improving the yield strength and optical properties of the optical film, the imidization rate is preferably above the above-mentioned lower limit. In addition, the upper limit of the imidization rate is 100% or less. The imidization rate represents the ratio of the value of the molar amount of the imide bond in the polyimide resin relative to the molar amount of the structural unit from the tetracarboxylic acid compound in the polyimide resin to twice. It should be noted that, in the case where the polyimide resin contains a tricarboxylic acid compound, the molar amount of the imide bond in the polyimide resin relative to the molar amount of the structural unit from the tetracarboxylic acid compound in the polyimide resin is expressed to be the ratio of the total value of the molar amount of the structural unit from the tricarboxylic acid compound. In addition, the imidization rate can be obtained by IR method, NMR method, etc.
[0205] <Method for producing polyimide resin>
[0206] The manufacturing method of the polyimide resin of the present invention is not particularly limited. In one embodiment of the present invention, the tetracarboxylic acid compound and the diamine compound described later can be used as the main raw materials, and the dicarboxylic acid compound can be used to manufacture according to the situation. More specifically, it can be manufactured by a method including the following steps: a step of reacting a diamine compound with a tetracarboxylic acid compound to obtain a polyamic acid, a step of reacting the polyamic acid with a dicarboxylic acid to obtain a polyamide-imide resin precursor in the case where the polyimide resin is a polyamide-imide resin, and a step of imidizing the polyamic acid or the polyamide-imide resin precursor. It should be noted that, in addition to tetracarboxylic acid compounds and dicarboxylic acid compounds, tricarboxylic acid compounds can also be reacted.
[0207] The structural units represented by formula (1) and formula (30) are usually derived from a diamine compound and a tetracarboxylic acid compound. The structural unit represented by formula (3) is usually derived from a diamine compound and a dicarboxylic acid compound. The structural unit represented by formula (31) is usually derived from a diamine compound and a tricarboxylic acid compound.
[0208] The tetracarboxylic acid compound used in the production of the polyimide resin preferably contains at least a compound represented by formula (X),
[0209] [Chemical formula 24]
[0210]
[0211] [In formula (X), R 1 ~R 5 , m and n are respectively the same as R in formula (3) 1 ~R 5 , m and n are the same].
[0212] The compound represented by formula (X) can be obtained by a conventional method, for example, by reacting trimellitic anhydride or a derivative thereof with an aromatic diol, or a commercially available product may be used.
[0213] In one embodiment of the present invention, the tetracarboxylic acid compound used in the production of the polyimide resin may further include a compound represented by formula (Y) in addition to the compound represented by formula (X).
[0214] [Chemical formula 25]
[0215]
[0216] [In formula (Y), B, R 7 and t are respectively related to B and R in formula (5) 7 Same as t].
[0217] As the tetracarboxylic acid compound used in the manufacture of the polyimide resin, there can be mentioned aromatic tetracarboxylic acid compounds such as aromatic tetracarboxylic dianhydride; and aliphatic tetracarboxylic acid compounds such as aliphatic tetracarboxylic dianhydride. The tetracarboxylic acid compound can be used alone or in combination of two or more. In addition to the dianhydride, the tetracarboxylic acid compound can also be a tetracarboxylic acid compound analog such as an acid chloride compound.
[0218] Specific examples of the aromatic tetracarboxylic dianhydride include non-condensed polycyclic aromatic tetracarboxylic dianhydrides, monocyclic aromatic tetracarboxylic dianhydrides, and condensed polycyclic aromatic tetracarboxylic dianhydrides. Examples of the non-condensed polycyclic aromatic tetracarboxylic dianhydrides include an ester of trimellitic anhydride and 2,2',3,3',5,5'-hexamethyl-4,4'-biphenol (hereinafter sometimes referred to as TAAMBP), an ester of trimellitic anhydride and 2,2',3,3'-tetramethyl-4,4'-biphenol (hereinafter sometimes referred to as TA23X-BP), an ester of trimellitic anhydride and 3,3 ',5,5'-tetramethyl-4,4'-biphenol esters, 4,4'-oxydiphthalic acid dianhydride, 3,3',4,4'-benzophenonetetracarboxylic acid dianhydride, 2,2',3,3'-benzophenonetetracarboxylic acid dianhydride, 3,3',4,4'-biphenyltetracarboxylic acid dianhydride (hereinafter sometimes referred to as BPDA), 2,2',3,3'-biphenyltetracarboxylic acid dianhydride, 3,3',4,4'- 4'-diphenylsulfonetetracarboxylic dianhydride, 2,2-bis(3,4-dicarboxyphenyl)propane dianhydride, 2,2-bis(2,3-dicarboxyphenyl)propane dianhydride, 2,2-bis(3,4-dicarboxyphenoxyphenyl)propane dianhydride, 4,4'-(hexafluoroisopropylidene)diphthalic dianhydride (hereinafter sometimes referred to as 6FDA), 1,2-bis(2,3-dicarboxyphenyl)ethane dianhydride, 1, 1-bis(2,3-dicarboxyphenyl)ethane dianhydride, 1,2-bis(3,4-dicarboxyphenyl)ethane dianhydride, 1,1-bis(3,4-dicarboxyphenyl)ethane dianhydride, bis(3,4-dicarboxyphenyl)methane dianhydride, bis(2,3-dicarboxyphenyl)methane dianhydride, 4,4'-(p-phenylenedioxy)diphthalic dianhydride, 4,4'-(isophenylenedioxy)diphthalic dianhydride. In addition, as a monocyclic aromatic tetracarboxylic dianhydride, for example, 1,2,4,5-pyromellitic dianhydride [also referred to as pyromellitic dianhydride (hereinafter, sometimes described as PMDA)] can be mentioned, and as a condensed polycyclic aromatic tetracarboxylic dianhydride, for example, 2,3,6,7-naphthalenetetracarboxylic dianhydride can be mentioned.
[0219] Among them, preferred are Tahmbp, TA23X-BP, an ester of trimellitic anhydride and 3,3',5,5'-tetramethyl-4,4'-biphenol, PMDA, 4,4'-oxydiphthalic dianhydride, 3,3',4,4'-benzophenonetetracarboxylic dianhydride, 2,2',3,3'-benzophenonetetracarboxylic dianhydride, 3,3',4,4'-biphenyltetracarboxylic acid dianhydride, anhydride, 2,2',3,3'-biphenyltetracarboxylic dianhydride, 3,3',4,4'-diphenylsulfonetetracarboxylic dianhydride, 2,2-bis(3,4-dicarboxyphenyl)propane dianhydride, 2,2-bis(2,3-dicarboxyphenyl)propane dianhydride, 2,2-bis(3,4-dicarboxyphenoxyphenyl)propane dianhydride, 6FDA, 1,2-bis(2,3-dicarboxyphenyl)ethane dianhydride, 1,1 -bis(2,3-dicarboxyphenyl)ethane dianhydride, 1,2-bis(3,4-dicarboxyphenyl)ethane dianhydride, 1,1-bis(3,4-dicarboxyphenyl)ethane dianhydride, bis(3,4-dicarboxyphenyl)methane dianhydride, bis(2,3-dicarboxyphenyl)methane dianhydride, 4,4'-(p-phenylenedioxy)diphthalic dianhydride and 4,4'-(isophenylenedioxy)diphthalic dianhydride , more preferably Tahmbp, TA23X-BP, an ester of trimellitic anhydride and 3,3',5,5'-tetramethyl-4,4'-biphenol, 4,4'-oxydiphthalic anhydride, BPDA, 2,2',3,3'-biphenyltetracarboxylic anhydride, 6FDA, bis(3,4-dicarboxyphenyl)methane dianhydride and 4,4'-(p-phenylenedioxy)diphthalic anhydride. These may be used alone or in combination of two or more.
[0220] As aliphatic tetracarboxylic dianhydride, cyclic or non-cyclic aliphatic tetracarboxylic dianhydride can be cited. Cyclic aliphatic tetracarboxylic dianhydride refers to a tetracarboxylic dianhydride having an alicyclic hydrocarbon structure. As specific examples thereof, cycloalkane tetracarboxylic dianhydrides such as 1,2,4,5-cyclohexanetetracarboxylic dianhydride, 1,2,3,4-cyclobutanetetracarboxylic dianhydride, 1,2,3,4-cyclopentanetetracarboxylic dianhydride, bicyclo[2.2.2]oct-7-ene-2,3,5,6-tetracarboxylic dianhydride, dicyclohexyl-3,3',4,4'-tetracarboxylic dianhydride and their positional isomers can be cited. These can be used alone or in combination of two or more. As specific examples of non-cyclic aliphatic tetracarboxylic dianhydride, 1,2,3,4-butanetetracarboxylic dianhydride and 1,2,3,4-pentanetetracarboxylic dianhydride can be cited, and these can be used alone or in combination of two or more. Moreover, you may use a cyclic aliphatic tetracarboxylic dianhydride and a non-cyclic aliphatic tetracarboxylic dianhydride in combination.
[0221] Among the above-mentioned tetracarboxylic dianhydrides, from the viewpoint of easily improving the yield strength and transparency of the optical film, preferred are TahmbP, TA23X-BP, an ester of trimellitic anhydride and 3,3',5,5'-tetramethyl-4,4'-biphenol, PMDA, 4,4'-oxydiphthalic anhydride, 3,3',4,4'-benzophenonetetracarboxylic anhydride, 3,3',4,4'-biphenyltetracarboxylic anhydride, 2,2',3,3'-biphenyltetracarboxylic anhydride, 3,3',4,4'-diphenylsulfonetetracarboxylic anhydride, 2,2-bis(3,4-dicarboxyphenyl)propane dianhydride, 6FDA, and a mixture thereof; and more preferred are TahmbP, TA23X-BP, an ester of trimellitic anhydride and 3,3',5,5'-tetramethyl-4,4'-biphenol, 6FDA, and a mixture thereof.
[0222] In the case where the polyimide resin is a polyamide-imide resin, examples of the dicarboxylic acid compound used in its synthesis include aromatic dicarboxylic acids, aliphatic dicarboxylic acids, and similar acid chloride compounds and acid anhydrides thereof, and two or more thereof may be used in combination. Specific examples include terephthalic acid; 2,5-bis(trifluoromethyl)terephthalic acid; isophthalic acid; 2,5-dimethylterephthalic acid; 2,5-dimethoxyterephthalic acid; naphthalene dicarboxylic acid; 4,4'-biphenyl dicarboxylic acid; 3,3'-biphenyl dicarboxylic acid; 2,2'-bis(trifluoromethyl)-4,4'-biphenyl dicarboxylic acid; a dicarboxylic acid compound of a chain hydrocarbon having 8 or less carbon atoms and two benzoic acids connected by a single bond, -CH 2 -、-C(CH 3 ) 2 -、-C(CF 3 ) 2 -、-SO 2 - or phenylene compounds, and their acid chloride compounds. Among these dicarboxylic acid compounds, from the viewpoint of easily improving the yield strength and transparency of the optical film, 4,4'-oxybisbenzoic acid, terephthalic acid, isophthalic acid, 2-methoxyterephthalic acid, 2,5-dimethylterephthalic acid, 2,5-dimethoxyterephthalic acid, 2,5-bis(trifluoromethyl)terephthalic acid, 2,2'-bis(trifluoromethyl)-4,4'-biphenyl dicarboxylic acid and their acid chlorides are preferred, and 4,4'-oxybis(phenylene)dicarboxylic acid is more preferred. Preferably, the present invention is characterized in that: terephthaloyl chloride (hereinafter, sometimes described as OMTPC), 2,5-dimethylterephthaloyl chloride (hereinafter, sometimes described as DMTPC), 2,5-dimethoxyterephthaloyl chloride, 2,5-bis(trifluoromethyl)terephthaloyl chloride, 2-methoxyterephthaloyl chloride (hereinafter, sometimes described as OMTPC), terephthaloyl chloride (hereinafter, sometimes described as TPC), isophthaloyl chloride, and more preferably TPC, 2,5-dimethoxyterephthaloyl chloride, DMTPC, and OMTPC.
[0223] The polyimide resin may be reacted with other tetracarboxylic acids and tricarboxylic acids, and their anhydrides and derivatives in addition to the tetracarboxylic acid compound used in the synthesis of the polyimide resin, within the range not impairing various physical properties of the optical film.
[0224] As other tetracarboxylic acids, water addition products of the acid anhydrides of the above-mentioned tetracarboxylic acid compounds can be mentioned.
[0225] Examples of tricarboxylic acid compounds include aromatic tricarboxylic acids, aliphatic tricarboxylic acids, and their similar acyl chloride compounds, anhydrides, and the like. Two or more of these may be used in combination. Specific examples include 1,2,4-benzenetricarboxylic acid anhydride; 2,3,6-naphthalenetricarboxylic acid-2,3-anhydride; phthalic anhydride and benzoic acid via single bonds, -O-, -CH 2 -、-C(CH 3 ) 2 -、-C(CF 3 ) 2 -、-SO 2 - or phenylene connected compounds.
[0226] As the diamine compound used in the synthesis of polyimide resin, for example, aliphatic diamine, aromatic diamine and mixtures thereof can be cited. It should be noted that, in the present embodiment, "aromatic diamine" means a diamine in which an amino group is directly bonded to an aromatic ring, and a part of its structure may include an aliphatic group or other substituents. The aromatic ring may be a monocyclic ring or a condensed ring, and examples thereof include a benzene ring, a naphthalene ring, an anthracene ring and a fluorene ring, but are not limited to these. Among them, a benzene ring is preferably used. In addition, "aliphatic diamine" means a diamine in which an amino group is directly bonded to an aliphatic group, and a part of its structure may include an aromatic ring and other substituents.
[0227] Examples of the aliphatic diamine include non-cyclic aliphatic diamines such as hexamethylenediamine, and cyclic aliphatic diamines such as 1,3-bis(aminomethyl)cyclohexane, 1,4-bis(aminomethyl)cyclohexane, norbornanediamine, and 4,4′-diaminodicyclohexylmethane. These can be used alone or in combination of two or more.
[0228] Examples of the aromatic diamine include aromatic diamines having one aromatic ring such as p-phenylenediamine, m-phenylenediamine, 2,4-toluenediamine, m-phenylenediamine, p-phenylenediamine, 1,5-diaminonaphthalene, and 2,6-diaminonaphthalene, 4,4'-diaminodiphenylmethane, 4,4'-diaminodiphenylpropane, 4,4'-diaminodiphenyl ether, 3,4'-diaminodiphenyl ether, 3,3'-diaminodiphenyl ether, 4,4'-diaminodiphenyl sulfone, 3,4'-diaminodiphenyl sulfone, 3,3'-diaminodiphenyl sulfone, 1,4-bis(4-aminophenoxy)benzene, 1,3-bis(4-aminophenoxy)benzene, bis[4-(4-aminophenoxy)phenyl]sulfone, bis[4-(3-aminophenoxy)phenyl]sulfone,
[0063] Aromatic diamines having two or more aromatic rings include 2,2-bis[4-(4-aminophenoxy)phenyl]sulfone, 2,2-bis[4-(4-aminophenoxy)phenyl]propane, 2,2-bis[4-(3-aminophenoxy)phenyl]propane, 2,2'-dimethylbenzidine, 2,2'-bis(trifluoromethyl)-4,4'-diaminobiphenyl (hereinafter, sometimes referred to as TFMB), 4,4'-(hexafluoropropylidene)diphenylamine (hereinafter, sometimes referred to as 6FDAM), 4,4'-bis(4-aminophenoxy)biphenyl, 9,9-bis(4-aminophenyl)fluorene, 9,9-bis(4-amino-3-methylphenyl)fluorene, 9,9-bis(4-amino-3-chlorophenyl)fluorene, and 9,9-bis(4-amino-3-fluorophenyl)fluorene. These may be used alone or in combination of two or more.
[0229] Preferred aromatic diamines include 4,4'-diaminodiphenylmethane, 4,4'-diaminodiphenylpropane, 4,4'-diaminodiphenyl ether, 3,3'-diaminodiphenyl ether, 4,4'-diaminodiphenyl sulfone, 3,3'-diaminodiphenyl sulfone, 1,4-bis(4-aminophenoxy)benzene, bis[4-(4-aminophenoxy)phenyl]sulfone, bis[4-(3-aminophenoxy)phenyl]sulfone, 2,2-bis[4-(4-aminophenoxy)phenyl]propane, 2,2-bis[4-(3-aminophenoxy)phenyl]propane, 2,2'-bis[4-(4-aminophenoxy)phenyl]propane, 2,2'-bis[4-(3-aminophenoxy)phenyl]propane, 2,2'-bis[4-(3-aminophenoxy)phenyl]propane, 2,2'-bis[4-(4-aminophenoxy)phenyl]sulfone, 2,2'-bis[4-(3-aminophenoxy)phenyl]sulfone, 2,2'-bis[4-(4-aminophenoxy)phenyl]propane, 2,2'-bis[4-(3-aminophenoxy)phenyl]propane, 2,2'-bis[4-(3-aminophenoxy)phenyl]sulfone, 2,2'-bis[4-(4-aminophenoxy)phenyl]sulfone, 2,2'-bis[4-(3-aminophenoxy)phenyl]sulfone, 2,2'-bis[4-(4-aminophenoxy)phenyl]propane, 2,2'-bis[4-(3-aminophenoxy)phenyl]sulfone, 2,2'-bis[4-(3-aminophenoxy)phenyl]sulfone, 2,2'-bis[4-(4-aminophenoxy)phenyl]sulfone, 2,2'-bis[4-(3-aminophenoxy)phenyl]sulfone, -dimethylbenzidine, TFMB, 6FDAM, 4,4'-bis(4-aminophenoxy)biphenyl, more preferably 4,4'-diaminodiphenylmethane, 4,4'-diaminodiphenylpropane, 4,4'-diaminodiphenyl ether, 4,4'-diaminodiphenyl sulfone, 1,4-bis(4-aminophenoxy)benzene, bis[4-(4-aminophenoxy)phenyl]sulfone, 2,2-bis[4-(4-aminophenoxy)phenyl]propane, 2,2'-dimethylbenzidine, TFMB, 6FDAM, 4,4'-bis(4-aminophenoxy)biphenyl. These may be used alone or in combination of two or more.
[0230] Among the above diamine compounds, from the viewpoint of easily improving the yield strength and transparency of the optical film, it is more preferable to use one or more selected from 2,2'-dimethylbenzidine, TFMB, 4,4'-bis(4-aminophenoxy)biphenyl, 6FDAM and 4,4'-diaminodiphenyl ether, and it is even more preferable to use TFMB and / or 6FDAM.
[0231] In the production of the polyimide-based resin, the usage-amounts of the diamine compound, the tetracarboxylic acid compound, and the dicarboxylic acid compound can be appropriately selected according to the ratio of each structural unit of the desired resin.
[0232] In a preferred embodiment of the present invention, the total molar amount of the tetracarboxylic acid compound and the dicarboxylic acid compound included according to the situation is set to 1 mole, and the usage of the diamine compound is preferably 0.94 mole or more, more preferably 0.96 mole or more, further preferably 0.98 mole or more, especially preferably 0.99 mole or more, preferably 1.20 mole or less, more preferably 1.10 mole or less, further preferably 1.05 mole or less, especially preferably 1.02 mole or less. If the usage of the diamine compound relative to the tetracarboxylic acid compound and the dicarboxylic acid compound included according to the situation is within the above range, even in the case where the polyimide resin has a structure shown in formula (2), it is easy to obtain a high molecular weight polyimide resin, as a result, it is easy to improve the yield strength and transparency of the obtained optical film.
[0233] The reaction temperature of the diamine compound and the tetracarboxylic acid compound is not particularly limited, for example, it can be 5 to 200°C, and the reaction time is not particularly limited, for example, it can be about 30 minutes to 72 hours. In a preferred embodiment of the present invention, even if the polyimide resin has a structure represented by formula (2), from the viewpoint of easily increasing the Mw of the polyimide resin, the reaction temperature is preferably 5 to 50°C, more preferably 5 to 40°C, and further preferably 5 to 25°C, and the reaction time is preferably 3 to 24 hours, more preferably 5 to 20 hours.
[0234] The reaction of the diamine compound and the tetracarboxylic acid compound is preferably carried out in a solvent. As the solvent, there is no particular limitation as long as it does not affect the reaction, for example, water, methanol, ethanol, ethylene glycol, isopropanol, propylene glycol, ethylene glycol methyl ether, ethylene glycol butyl ether, 1-methoxy-2-propanol, 2-butoxyethanol, propylene glycol monomethyl ether and other alcohol solvents; ethyl acetate, butyl acetate, ethylene glycol methyl ether acetate, γ-butyrolactone, γ-valerolactone, propylene glycol methyl ether acetate, ethyl lactate and other ester solvents; acetone, methyl ethyl ketone, cyclopentanone, cyclohexanone, 2-heptanone, methyl isobutyl ketone and other ketone solvents; pentane, hexane Aliphatic hydrocarbon solvents such as cyclohexane and heptane; alicyclic hydrocarbon solvents such as ethylcyclohexane; aromatic hydrocarbon solvents such as toluene and xylene; nitrile solvents such as acetonitrile; ether solvents such as tetrahydrofuran and dimethoxyethane; chlorinated solvents such as chloroform and chlorobenzene; amide solvents such as N,N-dimethylacetamide (hereinafter, sometimes recorded as DMAc) and N,N-dimethylformamide (hereinafter, sometimes recorded as DMF); sulfur-containing solvents such as dimethyl sulfone, dimethyl sulfoxide, and cyclopentane; carbonate solvents such as ethylene carbonate and propylene carbonate; and combinations thereof. Among them, amide solvents can be preferably used from the viewpoint of solubility.
[0235] In a preferred embodiment of the present invention, the solvent used in the reaction is preferably a solvent strictly dehydrated to a water content of 700 ppm or less. By adjusting the water content to the above range, even when the polyimide resin has a structure represented by formula (2), it is easy to polymerize the polyimide resin.
[0236] The reaction of the diamine compound and the tetracarboxylic acid compound may be carried out under an inert atmosphere such as a nitrogen atmosphere, an argon atmosphere or under reduced pressure as necessary. From the viewpoint of easily obtaining a high molecular weight polyimide resin, it is preferably carried out under the same inert atmosphere as above with stirring in a strictly controlled dehydrating solvent.
[0237] The production conditions of the polyamic acid and the dicarboxylic acid may be appropriately selected from the production conditions in the reaction of the diamine compound and the tetracarboxylic acid compound.
[0238] Examples of the imidization catalyst used in the imidization step include aliphatic amines such as tripropylamine, dibutylpropylamine, and ethyldibutylamine; alicyclic amines (monocyclic) such as N-ethylpiperidine, N-propylpiperidine, N-butylpyrrolidine, N-butylpiperidine, and N-propylhexahydroazepine; azabicyclo[2.2.1]heptane, azabicyclo[3.2.1]octane, azabicyclo[2.2.2]octane, and azabicyclo[3.2.2]nonane; Alicyclic amines (polycyclic) such as alkane; and aromatic amines such as pyridine, 2-picoline, 3-picoline, 4-picoline, 2-ethylpyridine, 3-ethylpyridine, 4-ethylpyridine, 2,4-dimethylpyridine, 2,4,6-trimethylpyridine, 3,4-cyclopentapyridine, 5,6,7,8-tetrahydroisoquinoline and isoquinoline. In addition, from the viewpoint of easily promoting the imidization reaction, it is preferred to use an acid anhydride together with the imidization catalyst. The acid anhydride can include conventional acid anhydrides used in the imidization reaction, and specific examples thereof include aliphatic acid anhydrides such as acetic anhydride, propionic anhydride, butyric anhydride, and aromatic acid anhydrides such as phthalic acid.
[0239] In a preferred embodiment of the present invention, it is preferred to carry out the imidization process in stages and heat it to the optimal reaction temperature. By carrying out the imidization in stages, it is easy to suppress the decomposition of the resin and easily obtain a high molecular weight polyimide resin. The reaction temperature of the heating of the imidization process carried out in stages is preferably 40 to 85 ° C, more preferably 45 to 80 ° C. If the reaction temperature is in the above range, there is a trend that the imidization reaction is fully advanced, and there is a trend that Mw is fully increased. The reaction time is preferably 30 minutes to 10 hours, more preferably 30 minutes to 5 hours. If the reaction time is in the above range, it is easy to suppress the decomposition of the resin and the decrease in Mw, and it is easy to suppress the decrease in the imidization rate and the low molecular weight in the subsequent process. In this way, in addition to the synthesis conditions described above, a high molecular weight resin can be obtained by controlling the imidization process.
[0240] For polyimide resins, they can be separated and purified by conventional methods, such as filtration, concentration, extraction, crystallization, recrystallization, column chromatography and other separation methods. In a preferred method, a large amount of alcohol such as methanol is added to the reaction solution containing the resin to precipitate the resin, and the separation is carried out by concentration, filtration, drying, etc.
[0241] <Additives>
[0242] The optical film of the present invention may further include at least one filler in addition to the polyimide resin. As fillers, for example, organic particles, inorganic particles, etc. may be cited, and inorganic particles may be preferably cited. As inorganic particles, metal oxide particles such as silicon dioxide, zirconium oxide, aluminum oxide, titanium dioxide, zinc oxide, germanium oxide, indium oxide, tin oxide, indium tin oxide, antimony oxide, cerium oxide, and metal fluoride particles such as magnesium fluoride and sodium fluoride may be cited, among which, from the viewpoint of easily improving the yield strength, elastic modulus and transparency of the optical film, silicon dioxide particles, zirconium oxide particles, aluminum oxide particles may be preferably cited, and silicon dioxide particles may be more preferably cited. These fillers may be used alone or in combination of two or more.
[0243] The average primary particle size of the filler, preferably the silica particles, is usually 1 nm or more, preferably 5 nm or more, more preferably 10 nm or more, further preferably 15 nm or more, especially preferably 20 nm or more, preferably 100 nm or less, more preferably 90 nm or less, further preferably 80 nm or less, further preferably 70 nm or less, especially preferably 60 nm or less, especially more preferably 50 nm or less, especially more preferably 40 nm or less. If the average primary particle size of the filler, preferably the silica particles, is within the above range, it is easy to improve the yield strength, elastic modulus and transparency of the optical film. In addition, it is easy to suppress the aggregation of the filler, preferably the silica particles, and it is easy to improve the transparency of the obtained optical film. The average primary particle size of the filler can be measured by the BET method. It should be noted that the average primary particle size can also be measured by image analysis of a transmission electron microscope or a scanning electron microscope.
[0244] In the case where the optical film of the present invention contains fillers, preferably silica particles, the content of the filler is usually 0.1% by mass or more, preferably 1% by mass or more, more preferably 5% by mass or more, further preferably 10% by mass or more, further preferably 20% by mass or more, particularly preferably 30% by mass or more, and preferably 60% by mass or less, relative to the mass of the optical film. If the content of the filler is above the lower limit, it is easy to improve the yield strength, elastic modulus and transparency of the optical film. In addition, if the content of the filler is below the upper limit, it is easy to improve the optical properties of the optical film.
[0245] The optical film of the present invention may further contain an ultraviolet absorber. The ultraviolet absorber can be appropriately selected from ultraviolet absorbers commonly used as ultraviolet absorbers in the field of resin materials. The ultraviolet absorber may contain a compound that absorbs light of a wavelength of 400nm or less. As the ultraviolet absorber, for example, at least one compound selected from benzophenone compounds, salicylate compounds, benzotriazole compounds and triazine compounds can be cited. The ultraviolet absorber can be used alone or in combination of two or more. By making the optical film contain an ultraviolet absorber, the degradation of the resin can be suppressed, so that the visual recognition can be improved when the optical film is applied to an image display device, etc. In this specification, a "series compound" refers to a derivative of a compound with the "series compound". For example, a "benzophenone series compound" refers to a compound having benzophenone as a parent skeleton and a substituent bonded to benzophenone.
[0246] When the optical film contains an ultraviolet absorber, the content of the ultraviolet absorber is preferably 1% by mass or more, more preferably 2% by mass or more, and further preferably 3% by mass or more, and preferably 10% by mass or less, more preferably 8% by mass or less, and further preferably 6% by mass or less, relative to the mass of the optical film. The preferred content varies depending on the ultraviolet absorber used, but if the content of the ultraviolet absorber is adjusted so that the light transmittance at 400 nm is about 20 to 60%, the light resistance of the optical film can be improved, and the transparency can be easily improved.
[0247] The optical film of the present invention may further contain other additives other than fillers and ultraviolet absorbers. As other additives, for example, antioxidants, release agents, stabilizers, bluing agents, flame retardants, pH adjusters, silica dispersants, lubricants, thickeners and leveling agents can be cited. In the case of containing other additives, their content is preferably 0.001 to 20% by mass, more preferably 0.01 to 15% by mass, and further preferably 0.1 to 10% by mass relative to the mass of the optical film.
[0248] The use of the optical film of the present invention is not particularly limited, and it can be used for various purposes. The optical film of the present invention can be a single layer or a laminate. The optical film of the present invention can be used directly or in the form of a laminate with other films. It should be noted that when the optical film is a laminate, all layers laminated on one side or both sides of the optical film are included in the optical film.
[0249] When the optical film of the present invention is a laminate, it is preferred that at least one surface of the optical film has one or more functional layers. As the functional layer, for example, a hard coat layer, a primer layer, a gas barrier layer, an ultraviolet absorbing layer, an adhesive layer, a color tone adjustment layer, a refractive index adjustment layer, etc. can be cited. The functional layer can be used alone or in combination of two or more.
[0250] The thickness of the hard coating layer is not particularly limited, and may be, for example, 2 to 100 μm. If the thickness of the hard coating layer is within the above range, the impact resistance can be improved, and the bending resistance is not easily reduced, and there is a tendency that the problem of curling caused by curing shrinkage is not easily caused. The hard coating layer can be formed by curing a hard coating composition containing a reactive material, and the reactive material can form a cross-linked structure by irradiation with active energy rays or thermal energy, and the hard coating layer is preferably formed by irradiation with active energy rays. Active energy rays are defined as energy rays that can decompose compounds that produce active species to produce active species, and examples include visible light, ultraviolet rays, infrared rays, X-rays, α rays, β rays, γ rays, and electron beams, and preferably ultraviolet rays. The hard coating composition contains at least one polymer selected from free radical polymerizable compounds and cationic polymerizable compounds.
[0251] The above-mentioned free radical polymerizable compound is a compound having a free radical polymerizable group. As the free radical polymerizable group possessed by the above-mentioned free radical polymerizable compound, as long as it is a functional group capable of undergoing free radical polymerization reaction, groups containing carbon-carbon unsaturated double bonds can be cited, and specifically, vinyl, (meth) acryloyl, etc. can be cited. It should be noted that, when the above-mentioned free radical polymerizable compound has more than two free radical polymerizable groups, these free radical polymerizable groups can be the same or different. From the aspect of improving the hardness of the hard coat layer, the number of free radical polymerizable groups possessed by the above-mentioned free radical polymerizable compound in one molecule is preferably more than 2. As the above-mentioned free radical polymerizable compound, from the aspect of high reactivity, a compound having a (meth)acryloyl group can be preferably mentioned, and specifically, a compound called a multifunctional acrylate monomer having 2 to 6 (meth)acryloyl groups in one molecule, and oligomers having a molecular weight of several hundred to several thousand and having a plurality of (meth)acryloyl groups in the molecule called epoxy (meth)acrylate, urethane (meth)acrylate, and polyester (meth)acrylate can be mentioned. Preferably, one or more selected from epoxy (meth)acrylate, urethane (meth)acrylate, and polyester (meth)acrylate can be mentioned.
[0252] The cationically polymerizable compound is a compound having a cationically polymerizable group such as an epoxy group, an oxetanyl group, a vinyl ether group, etc. From the perspective of increasing the hardness of the hard coat layer, the number of cationically polymerizable groups in one molecule of the cationically polymerizable compound is preferably 2 or more, more preferably 3 or more.
[0253] In addition, as the above-mentioned cationic polymerizable compound, it is preferred that the compound has at least one of epoxy and oxetane as a cationic polymerizable group. From the perspective of the small shrinkage associated with the polymerization reaction, cyclic ether groups such as epoxy and oxetane are preferred. In addition, the compound having an epoxy group in a cyclic ether group has the following advantages: it is easy to obtain a compound of a variety of structures, it will not adversely affect the durability of the obtained hard coat, and it is also easy to control the compatibility with the free radical polymerizable compound. In addition, the oxetane group in the cyclic ether group has the advantages of being easy to increase the degree of polymerization, accelerating the network formation speed obtained by the cationic polymerizable compound of the obtained hard coat, and forming an independent network in the region mixed with the free radical polymerizable compound without leaving unreacted monomers in the film.
[0254] Examples of the cationically polymerizable compound having an epoxy group include polyglycidyl ethers of polyols having an alicyclic ring, or alicyclic epoxy resins obtained by epoxidizing a compound containing a cyclohexene ring or a cyclopentene ring with an appropriate oxidizing agent such as hydrogen peroxide or a peracid; aliphatic epoxy resins such as polyglycidyl ethers of aliphatic polyols or alkylene oxide adducts thereof, polyglycidyl esters of aliphatic long-chain polybasic acids, and homopolymers and copolymers of glycidyl (meth)acrylate; glycidyl ethers produced by reacting bisphenols such as bisphenol A, bisphenol F, hydrogenated bisphenol A, or their derivatives such as alkylene oxide adducts and caprolactone adducts with epichlorohydrin; and glycidyl ether-type epoxy resins derived from bisphenols such as linear novolac epoxy resins.
[0255] The hard coating composition may further include a polymerization initiator. Examples of the polymerization initiator include free radical polymerization initiators, cationic polymerization initiators, free radical and cationic polymerization initiators, and the like, which can be appropriately selected and used. These polymerization initiators are decomposed by at least one of active energy ray irradiation and heating to generate free radicals or cations to promote free radical polymerization and cationic polymerization.
[0256] The radical polymerization initiator may be any one that can release a substance that initiates radical polymerization by at least one of irradiation with active energy rays and heating. For example, examples of thermal radical polymerization initiators include organic peroxides such as hydrogen peroxide and perbenzoic acid, and azo compounds such as azobisbutyronitrile.
[0257] As the active energy ray radical polymerization initiator, there are Type 1 radical polymerization initiators that generate radicals by decomposition of molecules and Type 2 radical polymerization initiators that generate radicals by hydrogen abstraction reaction in the presence of tertiary amines. These can be used alone or in combination.
[0258] The cationic polymerization initiator can release a substance that initiates cationic polymerization by at least one of active energy ray irradiation and heating. As the cationic polymerization initiator, aromatic iodonium salts, aromatic sulfonium salts, cyclopentadienyl iron (II) complexes, etc. can be used. They can initiate cationic polymerization by irradiating active energy rays or heating or both depending on the structure.
[0259] The hard coating composition may preferably contain 0.1 to 10% by mass of the polymerization initiator relative to 100% by mass of the entire composition. If the content of the polymerization initiator is within the above range, curing can be sufficiently advanced, and the mechanical properties and adhesion of the final coating film can be within a good range. In addition, there is a tendency that poor adhesion, cracking and curling due to curing shrinkage are less likely to occur.
[0260] The hard coating composition may further include one or more selected from a solvent and an additive.
[0261] The solvent can dissolve or disperse the polymerizable compound and the polymerization initiator, and any solvent known as a solvent for a hard coating composition in the art can be used within a range that does not inhibit the effects of the present invention.
[0262] The above-mentioned additives may further include inorganic particles, leveling agents, stabilizers, surfactants, antistatic agents, lubricants, antifouling agents, and the like.
[0263] The ultraviolet absorbing layer is a layer having an ultraviolet absorbing function, and is formed of, for example, a main material selected from ultraviolet curing transparent resins, electron beam curing transparent resins and thermosetting transparent resins, and an ultraviolet absorber dispersed in the main material.
[0264] The adhesive layer is a layer having an adhesive function, and has the function of bonding the optical film to other components. As the forming material of the adhesive layer, a commonly known material can be used. For example, a thermosetting resin composition or a photocurable resin composition can be used. In this case, by supplying energy afterwards, the thermosetting resin composition or the photocurable resin composition can be polymerized and cured.
[0265] The adhesive layer may be a layer called a pressure sensitive adhesive (PSA) that is attached to an object by pressing. A pressure sensitive adhesive may be an adhesive that is "a substance that has adhesive properties at room temperature and adheres to a bonded material with a light pressure" (JIS K 6800), or a capsule adhesive that is "an adhesive that contains a specific component in a protective film (microcapsule) and can maintain stability until the film is destroyed by an appropriate method (pressure, heat, etc.)" (JIS K 6800).
[0266] The color tone adjustment layer is a layer having a color tone adjustment function, and is a layer capable of adjusting the optical film to a target color tone. The color tone adjustment layer is, for example, a layer containing a resin and a colorant. Examples of the colorant include inorganic pigments such as titanium oxide, zinc oxide, red iron oxide, titanium oxide-based calcined pigments, ultramarine, cobalt aluminate, and carbon black; organic pigments such as azo compounds, quinacridone compounds, anthraquinone compounds, perylene compounds, isoindolinone compounds, phthalocyanine compounds, quinophthalone compounds, threne compounds, and diketopyrrolopyrrole compounds; body pigments such as barium sulfate and calcium carbonate; and dyes such as basic dyes, acid dyes, and mordant dyes.
[0267] The refractive index adjustment layer is a layer having a refractive index adjustment function, for example, a layer having a refractive index different from that of a single-layer optical film and capable of imparting a prescribed refractive index to the optical film. The refractive index adjustment layer may be, for example, a resin layer containing an appropriately selected resin and, depending on the circumstances, a pigment, or a metal film. Examples of pigments for adjusting the refractive index include silicon oxide, aluminum oxide, antimony oxide, tin oxide, titanium oxide, zirconium oxide, and tantalum oxide. The average primary particle size of the pigment may be 0.1 μm or less. By setting the average primary particle size of the pigment to be 0.1 μm or less, diffuse reflection of light passing through the refractive index adjustment layer can be prevented, and a reduction in transparency can be prevented. Examples of metals used in the refractive index adjustment layer include metal oxides or metal nitrides such as titanium oxide, tantalum oxide, zirconium oxide, zinc oxide, tin oxide, silicon oxide, indium oxide, titanium oxynitride, titanium nitride, silicon oxynitride, and silicon nitride.
[0268] In one embodiment of the present invention, the optical film may have a protective film on at least one side (single side or both sides). For example, in the case where a single side of the optical film has a functional layer, the protective film may be laminated on the surface of the optical film side or the surface of the functional layer side, or may be laminated on both sides of the optical film side and the functional layer side. In the case where both sides of the optical film have functional layers, the protective film may be laminated on the surface of one functional layer side, or may be laminated on the surfaces of two functional layer sides. The protective film is a film for temporarily protecting the surface of the optical film or the functional layer, and is not particularly limited as long as it is a peelable film that can protect the surface of the optical film or the functional layer. As a protective film, for example, polyester resin films such as polyethylene terephthalate, polybutylene terephthalate, and polyethylene naphthalate; polyolefin resin films such as polyethylene and polypropylene films, acrylic resin films, etc., are cited, preferably selected from polyolefin resin films, polyethylene terephthalate resin films, and acrylic resin films. In the case where the optical film has two protective films, each protective film may be the same or different.
[0269] The thickness of the protective film is not particularly limited, but is usually 10 to 120 μm, preferably 15 to 110 μm, and more preferably 20 to 100 μm. When the optical film has two protective films, the thickness of each protective film may be the same or different.
[0270] [Method for producing optical film]
[0271] The optical film of the present invention is not particularly limited, and can be produced, for example, by a method including the following steps.
[0272] (a) a step of preparing a liquid (sometimes referred to as a resin varnish) containing the polyimide resin (varnish preparation step);
[0273] (b) a step of applying a resin varnish to a substrate to form a coating film (coating step); and
[0274] (c) A step of drying the applied liquid (coating film) to form an optical film (optical film forming step).
[0275] In the varnish preparation step, the polyimide resin is dissolved in a solvent, and the additives are added as necessary, followed by stirring and mixing to prepare a resin varnish.
[0276] The solvent used in the preparation of the resin varnish is not particularly limited as long as it can dissolve the above-mentioned resin. As the solvent, for example, amide solvents such as DMAc and DMF; lactone solvents such as γ-butyrolactone and γ-valerolactone; sulfur-containing solvents such as dimethyl sulfone, dimethyl sulfoxide, and cyclopentane; carbonate solvents such as ethylene carbonate and propylene carbonate; and combinations thereof. Among them, amide solvents or lactone solvents are preferred. These solvents can be used alone or in combination of two or more. In addition, the resin varnish may contain water, alcohol solvents, ketone solvents, non-cyclic ester solvents, ether solvents, etc. The solid content concentration of the varnish is preferably 1 to 25% by mass, and more preferably 5 to 15% by mass. It should be noted that in this specification, the solid content of the varnish represents the total amount of the components after removing the solvent from the varnish.
[0277] In the coating step, a varnish is applied to the substrate by a known coating method to form a coating film. Examples of known coating methods include wire bar coating, reverse coating, roll coating such as gravure coating, die coating, comma coating, lip coating, spin coating, screen coating, injection coating, dipping, spraying, and tape casting.
[0278] In the optical film forming process, the optical film can be formed by drying the coating and peeling it from the substrate. After peeling, a drying process for drying the optical film can be further performed. The drying of the coating can usually be performed at a temperature of 50 to 350° C., preferably 50 to 230° C. In a preferred embodiment of the present invention, it is preferred to dry in stages. Varnishes containing high molecular weight resins tend to become high viscosity, and it is usually difficult to obtain a uniform film and a film with excellent transparency. Therefore, by drying in stages, the varnish containing high molecular weight resins can be dried uniformly. As needed, the coating can be dried under an inert atmosphere or under reduced pressure. In addition, if the optical film is dried under vacuum conditions, tiny bubbles are sometimes generated and remain in the film, which becomes the main reason for the reduction in transparency, so it is preferably carried out under atmospheric pressure.
[0279] Examples of substrates include PET films, PEN films, other polyimide resins, or polyamide resin films, etc. Among them, PET films and PEN films are preferred from the viewpoint of excellent heat resistance, and PET films are more preferred from the viewpoint of adhesion to optical films and cost.
[0280] The optical film of the present invention can be suitably used as a display device, especially a front panel (sometimes referred to as a window film) of a flexible display device, especially a front panel of a roll-up display or a foldable display. That is, the optical film of the present invention is preferably a film for a front panel of a flexible display device. The front panel has the function of protecting the display element of the flexible display device. It should be noted that a flexible display device refers to a display device used with operations such as repeated bending and repeated winding of an image display device. For the front panel of such a flexible display device used with repeated bending operations, etc., high bending resistance, especially high folding resistance, is required. In addition, high visual recognition is also required for the front panel. Compared with the film for the substrate of the image display device used inside the image display device, the film for the front panel of the image display device, especially the front panel of the flexible display device, requires high visual recognition and high bending resistance. For example, from the viewpoint of easily improving the visual recognition when used as a front panel for a flexible display device, the film of the present invention preferably has the total light transmittance, haze and / or YI value recorded above, and from the viewpoint of easily improving the bending resistance, especially the folding resistance when used as a front panel for a flexible display device, it is preferred to meet the folding number of times in the MIT folding fatigue test recorded above. As a display device, wearable devices such as televisions, smart phones, mobile phones, car navigation, tablet PCs, portable game consoles, electronic paper, indicators, bulletin boards, clocks and smart watches can be cited. As a flexible display, a display device with flexible characteristics can be cited, such as a television, a smart phone, a mobile phone, a smart watch, etc. As a flexible display device, all image display devices with flexible characteristics can be cited, for example, a rollable display and a foldable display as described above can be cited. A rollable display refers to an image display device in which the image display portion of the front panel is rolled up into a roll, and the image display device used in a state where the image display portion is drawn out and made into a plane or a curved surface is an image display device that is rolled up into a roll each time it is used. In addition, a foldable display refers to an image display device in which the image display portion including the front panel is bent and used in a state where the image display portion is unfolded to form a flat surface or a curved surface, and is an image display device that is bent and the like each time it is used. Such an image display device that is repeatedly rolled up, bent, and the like is called a flexible image display device.
[0281] 〔Flexible display device〕
[0282] The present invention also provides a flexible display device having an optical film of the present invention. The optical film of the present invention is preferably used as a front panel in a flexible display device, and the front panel is sometimes referred to as a window film. The flexible display device includes a laminate for a flexible display device and an organic EL display panel, and the laminate for a flexible display device is arranged on the visual recognition side relative to the organic EL display panel, and is configured in a bendable manner. As a laminate for a flexible display device, a polarizing plate and a touch sensor may be further contained, and their stacking order is arbitrary, preferably stacked in the order of a window film, a polarizing plate, a touch sensor or a window film, a touch sensor, and a polarizing plate from the visual recognition side. If a polarizing plate is present at a position closer to the visual recognition side than the touch sensor, the pattern of the touch sensor is not easily visually recognized, and the visual recognition of the displayed image becomes good, so it is preferred. Each component can be stacked using an adhesive, an adhesive, etc. In addition, a shading pattern formed on at least one side of any layer of the above-mentioned window film, polarizing plate, and touch sensor may be provided.
[0283] <Polarizing plate>
[0284] As described above, the flexible display device of the present invention is preferably further provided with a polarizing plate, wherein it is preferably further provided with a circular polarizing plate. A circular polarizing plate is a functional layer having the function of transmitting only right-handed circularly polarized light or left-handed circularly polarized light components by stacking a λ / 4 phase difference plate on a linear polarizing plate. For example, it is used to convert external light into right-handed circularly polarized light and block external light reflected by an organic EL panel to become left-handed circularly polarized light, so that only the luminous component of the organic EL is transmitted, thereby suppressing the influence of reflected light and making it easy to observe the image. In order to achieve the circularly polarized light function, the absorption axis of the linear polarizing plate and the slow axis of the λ / 4 phase difference plate theoretically need to be 45°, but in practical applications, it is 45±10°. The linear polarizing plate and the λ / 4 phase difference plate do not have to be stacked adjacent to each other, as long as the relationship between the absorption axis and the slow axis satisfies the above range. It is preferred to achieve complete circularly polarized light at all wavelengths, but this is not necessary in practical applications, so the circular polarizing plate in the present invention also includes an elliptical polarizing plate. It is also preferable to further laminate a λ / 4 phase difference film on the viewing side of the linear polarizing plate to make the emitted light circularly polarized, thereby improving visibility in a state where polarized sunglasses are worn.
[0285] The linear polarizing plate is a functional layer having the following functions: allowing light vibrating in the transmission axis direction to pass through, while blocking polarized light of the vibration component perpendicular thereto. The linear polarizing plate may be a single linear polarizer or a linear polarizer and a protective film attached to at least one side thereof. The thickness of the linear polarizing plate may be 200 μm or less, preferably 0.5 to 100 μm. If the thickness of the linear polarizing plate is within the above range, there is a tendency that the flexibility of the linear polarizing plate is not easily reduced.
[0286] The linear polarizer may be a film-type polarizer manufactured by dyeing and stretching a polyvinyl alcohol (hereinafter, sometimes abbreviated as PVA) film. By adsorbing dichroic pigments such as iodine on the PVA film that has been oriented by stretching, or by stretching the film while adsorbed on PVA, the dichroic pigment is oriented to exert polarization performance. In the manufacture of the film-type polarizer, there may also be steps such as swelling, cross-linking based on boric acid, washing with an aqueous solution, and drying. The stretching and dyeing steps may be performed in the form of a single PVA film or in a state of being stacked with other films such as polyethylene terephthalate. The thickness of the PVA film used is preferably 10 to 100 μm, and the stretching ratio is preferably 2 to 10 times.
[0287] In addition, as another example of the polarizer, a liquid crystal coated polarizer formed by coating a liquid crystal polarizing composition can be cited. The liquid crystal polarizing composition can include a liquid crystal compound and a dichroic pigment compound. The liquid crystal compound has the property of presenting a liquid crystal state, and is preferably capable of exerting high polarization performance when it has a high-order orientation state such as a smectic phase. In addition, the liquid crystal compound preferably has a polymerizable functional group.
[0288] The dichroic dye compound is a dye that exhibits dichroism when aligned together with the liquid crystal compound, and may have a polymerizable functional group. Furthermore, the dichroic dye itself may have liquid crystallinity.
[0289] Any of the compounds contained in the liquid crystal polarizing composition has a polymerizable functional group. The liquid crystal polarizing composition may further contain an initiator, a solvent, a dispersant, a leveling agent, a stabilizer, a surfactant, a crosslinking agent, a silane coupling agent, and the like.
[0290] The liquid crystal polarizing layer is produced by coating a liquid crystal polarizing composition on an alignment film to form a liquid crystal polarizing layer. The liquid crystal polarizing layer can be formed thinner than a film-type polarizing plate, and its thickness is preferably 0.5 to 10 μm, more preferably 1 to 5 μm.
[0291] The above-mentioned oriented film is manufactured, for example, by coating an oriented film forming composition on a substrate and imparting orientation by friction, polarized light irradiation, etc. The above-mentioned oriented film forming composition contains an oriented agent and may also contain a solvent, a cross-linking agent, an initiator, a dispersant, a leveling agent, a silane coupling agent, etc. As the above-mentioned oriented agent, for example, polyvinyl alcohols, polyacrylates, polyamic acids, and polyimides can be cited. In the case of using an oriented agent that imparts orientation by polarized light irradiation, it is preferred to use an oriented agent containing a cinnamate group. The Mw of the polymer used as the above-mentioned oriented agent is, for example, about 10000 to 1000000. The thickness of the above-mentioned oriented film is preferably 5 to 10000 nm, and from the perspective of fully demonstrating the orientation control force, it is more preferably 10 to 500 nm.
[0292] The liquid crystal polarizing layer may be laminated after being peeled from the substrate and then transferred, or may be directly laminated on the substrate. The substrate may also preferably function as a transparent substrate for a protective film, a phase difference plate, or a window film.
[0293] As the above-mentioned protective film, a transparent polymer film can be used, and the same materials and additives as those used in the transparent substrate of the above-mentioned window film can be used. In addition, it can be a coating type protective film obtained by coating a cationic curing composition such as an epoxy resin, a free radical curing composition such as an acrylate, and curing it. The protective film can contain a colorant such as a plasticizer, an ultraviolet absorber, an infrared absorber, a pigment, a dye, a fluorescent brightener, a dispersant, a heat stabilizer, a light stabilizer, an antistatic agent, an antioxidant, a lubricant, a solvent, etc. as needed. The thickness of the protective film is preferably less than 200 μm, and more preferably 1 to 100 μm. If the thickness of the protective film is in the above range, there is a tendency that the softness of the film is not easy to reduce.
[0294] The λ / 4 phase difference plate is a film that imparts a phase difference of λ / 4 in a direction orthogonal to the direction of travel of the incident light (in-plane direction of the film). The λ / 4 phase difference plate can be a stretched phase difference plate manufactured by stretching a polymer film such as a cellulose film, an olefin film, or a polycarbonate film. The λ / 4 phase difference plate can include a phase difference regulator, a plasticizer, an ultraviolet absorber, an infrared absorber, a pigment, a colorant such as a dye, a fluorescent whitening agent, a dispersant, a heat stabilizer, a light stabilizer, an antistatic agent, an antioxidant, a lubricant, a solvent, etc. as needed.
[0295] The thickness of the stretched phase difference plate is preferably 200 μm or less, and more preferably 1 to 100 μm. If the thickness of the stretched phase difference plate is within the above range, the flexibility of the stretched phase difference plate tends to be less likely to decrease.
[0296] Furthermore, as another example of the λ / 4 phase difference plate, there can be mentioned a liquid crystal coating type phase difference plate formed by coating a liquid crystal composition.
[0297] The liquid crystal composition includes a liquid crystal compound that exhibits a liquid crystal state such as a nematic, cholesteric, or smectic state. The liquid crystal compound has a polymerizable functional group.
[0298] The liquid crystal composition may further include an initiator, a solvent, a dispersant, a leveling agent, a stabilizer, a surfactant, a crosslinking agent, a silane coupling agent, and the like.
[0299] The above-mentioned liquid crystal coating type phase difference plate can be manufactured by coating a liquid crystal composition on a substrate and curing it to form a liquid crystal phase difference layer, similarly to the above-mentioned liquid crystal polarizing layer. The liquid crystal coating type phase difference plate can be formed to be thinner than the stretched phase difference plate. The thickness of the above-mentioned liquid crystal polarizing layer is preferably 0.5 to 10 μm, and more preferably 1 to 5 μm.
[0300] The liquid crystal coating type phase difference plate may be peeled from the substrate and then transferred and laminated, or the substrate may be directly laminated. The substrate also preferably functions as a transparent substrate for a protective film, a phase difference plate, or a window film.
[0301] Usually, the shorter the wavelength, the greater the birefringence, and the longer the wavelength, the smaller the birefringence. There are more materials. In this case, it is impossible to achieve a phase difference of λ / 4 in the entire visible light region. Therefore, in order to become λ / 4 near 560nm with high visibility, it can be designed in a way that the in-plane phase difference is preferably 100 to 180nm, more preferably 130 to 150nm. The reverse dispersion λ / 4 phase difference plate using a material having a birefringence wavelength dispersion characteristic opposite to the usual is preferred from the perspective of good visual recognition. As such a material, for example, with respect to a stretched phase difference plate, the material described in Japanese Patent Publication No. 2007-232873, etc. can be used, and with respect to a liquid crystal coated phase difference plate, a liquid crystal coated phase difference plate described in Japanese Patent Publication No. 2010-30979, etc. can be used.
[0302] In addition, as another method, it is also known that a wideband λ / 4 phase difference plate is obtained by combining with a λ / 2 phase difference plate (for example, Japanese Patent Publication No. 10-90521, etc.). The λ / 2 phase difference plate is also manufactured using the same material method as the λ / 4 phase difference plate. The combination of the stretched phase difference plate and the liquid crystal coated phase difference plate is arbitrary, but the thickness can be thinned by using a liquid crystal coated phase difference plate.
[0303] For the circular polarizing plate, in order to improve the visual recognition in the tilted direction, a method of stacking a positive C plate is known (for example, Japanese Patent Publication No. 2014-224837, etc.). The positive C plate can be a liquid crystal coated phase difference plate or a stretched phase difference plate. The phase difference in the thickness direction of the phase difference plate is preferably -200 to -20nm, more preferably -140 to -40nm.
[0304] 〔Touch sensor〕
[0305] As described above, the flexible display device of the present invention preferably further includes a touch sensor. The touch sensor can be used as an input mechanism. As the touch sensor, various methods such as a resistive film method, a surface elastic wave method, an infrared method, an electromagnetic induction method, and an electrostatic capacitance method can be cited, and the electrostatic capacitance method can be cited preferably.
[0306] The electrostatic capacitance touch sensor can be divided into an active area and an inactive area located in the periphery of the active area. The active area is the area corresponding to the area (display part) where the screen is displayed on the display panel, and is the area that senses the user's touch. The inactive area is the area corresponding to the area (non-display part) where the screen is not displayed in the display device. The touch sensor may include: a substrate with flexible characteristics; a sensing pattern formed in the active area of the substrate; and sensing lines formed in the inactive area of the substrate and used to connect the sensing pattern to an external driving circuit via a pad. As a substrate with flexible characteristics, the same material as the transparent substrate of the window film can be used.
[0307] The above-mentioned sensing pattern may include a first pattern formed along a first direction and a second pattern formed along a second direction. The first pattern and the second pattern are arranged in different directions from each other. The first pattern and the second pattern are formed on the same layer, and in order to sense the touched position, each pattern must be electrically connected. The first pattern is a form in which a plurality of unit patterns are interconnected via a connector, and the second pattern is a structure in which a plurality of unit patterns are separated from each other in the form of islands, so in order to electrically connect the second pattern, an additional bridge electrode is required. As an electrode for connecting the second pattern, a known transparent electrode can be applied. As the raw material of the transparent electrode, for example, indium tin oxide (ITO), indium zinc oxide (IZO), zinc oxide (ZnO), indium zinc tin oxide (IZTO), indium gallium zinc oxide (IGZO), cadmium tin oxide (CTO), PEDOT (poly (3,4-ethylenedioxythiophene)), carbon nanotubes (CNT), graphene and metal wires, etc., preferably ITO can be mentioned. These can be used alone or in combination of two or more. The metal used in the metal wire is not particularly limited, and for example, silver, gold, aluminum, copper, iron, nickel, titanium, selenium and chromium can be mentioned, and these can be used alone or in combination of two or more.
[0308] The bridge electrode may be formed on the upper part of the sensing pattern through the insulating layer, and the bridge electrode may be formed on the substrate, and the insulating layer and the sensing pattern may be formed thereon. The bridge electrode may be formed of the same raw material as the sensing pattern, or may be formed of molybdenum, silver, aluminum, copper, palladium, gold, platinum, zinc, tin, titanium, or an alloy of two or more thereof.
[0309] The first pattern and the second pattern must be electrically insulated, so an insulating layer is formed between the sensing pattern and the bridge electrode. The insulating layer can be formed only between the contact of the first pattern and the bridge electrode, or can be formed as a layer covering the entire sensing pattern. In the case of a layer covering the entire sensing pattern, the bridge electrode can be connected to the second pattern via a contact hole formed in the insulating layer.
[0310] For the above-mentioned touch sensor, as a means for appropriately compensating for the difference in transmittance between the pattern area where the sensing pattern is formed and the non-pattern area where the sensing pattern is not formed, specifically, the difference in transmittance caused by the difference in refractive index in these areas, an optical adjustment layer may be further included between the substrate and the electrode. The optical adjustment layer may contain an inorganic insulating substance or an organic insulating substance. The optical adjustment layer may be formed by applying a photocurable composition containing a photocurable organic binder and a solvent on a substrate. The above-mentioned photocurable composition may also contain inorganic particles. The above-mentioned inorganic particles can increase the refractive index of the optical adjustment layer.
[0311] The photocurable organic binder may include copolymers of monomers such as acrylate monomers, styrene monomers, and carboxylic acid monomers within a range that does not impair the effects of the present invention. The photocurable organic binder may be, for example, a copolymer including repeating units different from each other such as repeating units containing epoxy groups, acrylate repeating units, and carboxylic acid repeating units.
[0312] Examples of the inorganic particles include zirconium oxide particles, titanium dioxide particles, and aluminum oxide particles.
[0313] The photocurable composition may further contain additives such as a photopolymerization initiator, a polymerizable monomer, and a curing aid.
[0314] 〔Adhesive layer〕
[0315] Each layer (window film, circular polarizing plate, touch sensor) forming the above-mentioned flexible display device laminate and the film components (linear polarizing plate, λ / 4 phase difference plate, etc.) constituting each layer can be joined by an adhesive. As the adhesive, an aqueous adhesive, an organic solvent system, a solvent-free adhesive, a solid adhesive, a solvent volatile adhesive, an aqueous solvent volatile adhesive, a moisture-curing adhesive, a heat-curing adhesive, an anaerobic curing type, an active energy ray-curing adhesive, a curing agent mixed adhesive, a hot melt adhesive, a pressure-sensitive adhesive (adhesive), a rewetting adhesive and the like commonly used adhesives can be used, and aqueous solvent volatile adhesives, active energy ray-curing adhesives, adhesives can be preferably used. The thickness of the adhesive layer can be appropriately adjusted according to the required bonding force, etc., preferably 0.01 to 500 μm, more preferably 0.1 to 300 μm. The laminate for the flexible display device includes a plurality of adhesive layers, and the thickness and type of the adhesive layers may be the same or different.
[0316] As the above-mentioned water-based solvent volatile adhesive, water-soluble polymers such as polyvinyl alcohol polymers, starch, ethylene-vinyl acetate emulsions, styrene-butadiene emulsions, etc., in a water-dispersed state, can be used as the main polymer. In addition to the above-mentioned main polymer and water, a cross-linking agent, a silane compound, an ionic compound, a cross-linking catalyst, an antioxidant, a dye, a pigment, an inorganic filler, an organic solvent, etc. can also be used. In the case of bonding using the above-mentioned water-based solvent volatile adhesive, the above-mentioned water-based solvent volatile adhesive can be injected between the bonded layers, and the bonded layers can be dried after being laminated to impart adhesion. In the case of using the above-mentioned water-based solvent volatile adhesive, the thickness of the adhesive layer is preferably 0.01 to 10 μm, and more preferably 0.1 to 1 μm. In the case of using the above-mentioned water-based solvent volatile adhesive for multiple layers, the thickness and type of each layer can be the same or different.
[0317] The active energy ray-curable adhesive may be formed by curing an active energy ray-curable composition containing a reactive material that forms an adhesive layer by irradiating active energy rays. The active energy ray-curable composition may contain at least one polymer of a radical polymerizable compound and a cation polymerizable compound that are the same as the polymer contained in the hard coating composition. The radical polymerizable compound may be the same compound as the radical polymerizable compound in the hard coating composition.
[0318] The cationically polymerizable compound may be the same compound as that in the hard coating composition.
[0319] As the cationically polymerizable compound used in the active energy ray-curable composition, an epoxy compound is preferred. In order to reduce the viscosity of the adhesive composition, it is also preferred to contain a monofunctional compound as a reactive diluent.
[0320] In order to reduce the viscosity, the active energy ray composition may contain a monofunctional compound. Examples of the monofunctional compound include an acrylate monomer having one (meth)acryloyl group in one molecule, and a compound having one epoxy group or oxetanyl group in one molecule, such as glycidyl (meth)acrylate.
[0321] The active energy ray composition may further include a polymerization initiator. As the polymerization initiator, free radical polymerization initiators, cationic polymerization initiators, free radical and cationic polymerization initiators, etc. can be cited, and they can be appropriately selected for use. These polymerization initiators are decomposed by at least one of active energy ray irradiation and heating to generate free radicals or cations, thereby promoting free radical polymerization and cationic polymerization. An initiator that can initiate free radical polymerization or cationic polymerization by active energy ray irradiation in the hard coating composition can be used.
[0322] The above-mentioned active energy ray curing composition may further contain an ion trapping agent, an antioxidant, a chain transfer agent, a close adhesion imparting agent, a thermoplastic resin, a filler, a flow viscosity modifier, a plasticizer, a defoaming agent solvent, an additive, and a solvent. In the case where two adhered layers are bonded by the above-mentioned active energy ray curing adhesive, the bonding can be carried out in the following manner: the above-mentioned active energy ray curing composition is applied to any one or both of the adhered layers and then bonded, and any one or both of the adhered layers are irradiated with active energy rays to cure them. When the above-mentioned active energy ray curing adhesive is used, the thickness of the adhesive layer is preferably 0.01 to 20 μm, and more preferably 0.1 to 10 μm. When the above-mentioned active energy ray curing adhesive is used to form multiple adhesive layers, the thickness and type of each layer may be the same or different.
[0323] As the above-mentioned adhesive, it can be classified into acrylic adhesive, urethane adhesive, rubber adhesive, silicone adhesive, etc. according to the main polymer, and all of them can be used. In the adhesive, in addition to the main polymer, a crosslinking agent, a silane compound, an ionic compound, a crosslinking catalyst, an antioxidant, a tackifier, a plasticizer, a dye, a pigment, an inorganic filler, etc. can also be used. The components constituting the above-mentioned adhesive are dissolved and dispersed in a solvent to obtain an adhesive composition, and the adhesive composition is applied to a substrate and then dried to form an adhesive layer adhesive layer. The adhesive layer can be formed directly, or the adhesive layer formed separately on the substrate can be transferred. In order to cover the adhesive surface before bonding, it is also preferred to use a release film. In the case of using the above-mentioned active energy ray-curable adhesive, the thickness of the adhesive layer is preferably 0.1 to 500 μm, and more preferably 1 to 300 μm. In the case of using multiple layers of the above-mentioned adhesive, the thickness and type of each layer can be the same or different.
[0324] 〔Shading pattern〕
[0325] The above-mentioned shading pattern can be applied as at least a part of the frame or shell of the above-mentioned flexible display device. By using the shading pattern to hide the wiring arranged at the edge of the above-mentioned flexible display device so that it is not easy to be visually recognized, the visual recognizability of the image is improved. The above-mentioned shading pattern can be in the form of a single layer or a multilayer. The color of the shading pattern is not particularly limited, and can be a variety of colors such as black, white, and metallic colors. The shading pattern can be formed by a pigment for presenting color and a polymer such as an acrylic resin, an ester resin, an epoxy resin, a polyurethane, and a silicone. They can be used alone or in the form of a mixture of two or more. The above-mentioned shading pattern can be formed by various methods such as printing, photolithography, and inkjet. The thickness of the shading pattern is preferably 1 to 100 μm, and more preferably 2 to 50 μm. In addition, it is also preferred to give a shape such as an inclination in the thickness direction of the shading pattern.
[0326] Example
[0327] Hereinafter, the present invention will be described in further detail by way of Examples. "%" and "parts" in the Examples refer to mass % and mass parts unless otherwise specified. First, the evaluation method will be described.
[0328] <Determination of yield strength>
[0329] The yield strength of the optical films obtained in Examples and Comparative Examples was measured using "Autograph AG-IS" manufactured by Shimadzu Corporation. A film having a width of 10 mm was prepared and a stress-strain curve (SS curve) was measured under the conditions of a chuck distance of 50 mm and a tensile speed of 10 mm / min.
[0330] 1. Data collation of SS curve
[0331] Continuously sample 10 points from the measurement start point in the SS curve and fit it to a quadratic function using the least squares method. Then, fit the quadratic function of the 10-point sampling range until it becomes convex upward, remove 1 point from the left side of the measurement start point, and add 1 point to the right side. End data sorting when the fitting function becomes convex upward.
[0332] 2. Calculation of the tangent equation of the SS curve
[0333] Using the data of 1., the slope and intercept are obtained by the least square method. Then, for the j-1 slopes, the kth (k=1~48) to 49th data are fitted to a linear function by the least square method, and the slope when the strain is 0 is obtained by extrapolation. The central value of the 48 points obtained is defined as the slope of the straight line when the strain is 0 (SS curve tangent). The intercept is calculated in the same way to obtain the equation of the tangent of the SS curve when the strain is 0.
[0334] 3. Calculation of yield strength
[0335] The tangent line of the SS curve obtained in 2. when the strain is 0 is parallelized by 0.2% in the strain direction. The stress value at which the measured stress data exceeds the stress data of the parallelized straight line is taken as the yield strength.
[0336] <Total light transmittance>
[0337] The total light transmittance (Tt) of the optical films obtained in Examples and Comparative Examples was measured using a fully automatic direct-reading haze computer HGM-2DP manufactured by Suga Test Instruments Co., Ltd. in accordance with JIS K 7105:1981.
[0338] <Haze>
[0339] According to JIS K 7105: 1981, the optical films obtained in Examples and Comparative Examples were cut into a size of 30 mm×30 mm, and the haze was measured using a fully automatic direct-reading haze computer HGM-2DP manufactured by Suga Test Instruments.
[0340] <YI value>
[0341] The tristimulus values (X, Y, Z) of the optical films obtained in Examples and Comparative Examples were determined using an ultraviolet-visible-near-infrared spectrophotometer (V-670 manufactured by JASCO Corporation), and the tristimulus values (X, Y, Z) were substituted into the following calculation formula to calculate the YI value.
[0342] YI=100×(1.2769X-1.0592Z) / Y
[0343] <Elastic modulus>
[0344] The elastic modulus of the optical films obtained in the examples and comparative examples was measured using "Autograph AG-IS" manufactured by Shimadzu Corporation. A film with a width of 10 mm in length and width was prepared, and a stress-strain curve (SS curve) was measured under the conditions of a chuck distance of 50 mm and a tensile speed of 10 mm / min, and the elastic modulus was calculated from the slope.
[0345] <Evaluation of folding resistance>
[0346] According to ASTM standard D2176-16, the number of bends of the optical film in the examples and comparative examples is calculated as follows. The optical film is cut into strips of 15 mm × 100 mm using a dumbbell cutter. The cut optical film is placed on the main body of an MIT folding fatigue tester ("Model 0530", manufactured by Toyo Seiki Seisaku-sho, Ltd.), and the number of reciprocating bends in the front and back directions until the optical film breaks is measured under the conditions of a test speed of 175 cpm, a bending angle of 135°, a load of 0.75 kgf, and a bending fixture radius of R = 1 mm. This is taken as the number of bends (also called the number of folds).
[0347] <Measurement of thickness>
[0348] The thickness of the optical films obtained in Examples and Comparative Examples was measured using an ABS digital indicator (manufactured by Mitutoyo Corporation, “ID-C112BS”).
[0349] <Measurement of Mw>
[0350] GPC determination
[0351] (1) Pretreatment method
[0352] To the polyamide-imide resin obtained in the examples and comparative examples, a DMF eluent (a solution containing 10 mmol / L lithium bromide) was added to give a concentration of 2 mg / mL, and the mixture was heated at 80°C while stirring for 30 minutes. After cooling, the mixture was filtered through a 0.45 μm membrane filter and the resulting solution was used as a measurement solution.
[0353] (2) Measurement conditions
[0354] Column: TSKgel α-2500 ((7) 7.8 mm diameter × 300 mm) × 1 column, α-M ((13) 7.8 mm diameter × 300 mm) × 2 columns manufactured by Tosoh Corporation
[0355] Eluent: DMF (10 mmol / L lithium bromide added)
[0356] Flow rate: 1.0mL / min
[0357] Detector: RI detector
[0358] Column temperature: 40°C
[0359] Injection volume: 100 μL
[0360] Molecular weight standard: Standard polystyrene
[0361] <Synthesis Example 1: Production of polyamide-imide resin (1)>
[0362] Under a nitrogen atmosphere, TFMB and DMAc that was strictly dehydrated to a water content of less than 700 ppm were added to a separable flask equipped with a stirring blade, so that the solid content of TFMB was 5.13% by mass, and TFMB was dissolved in DMAc while stirring at room temperature. Next, 6FDA and TahmbP were added to the flask so that they were 20.20 mol% respectively relative to TFMB, and stirred at room temperature for 16 hours. Then, after cooling to 10°C, TPC was added in a manner that was 27.27 mol% relative to TFMB, and after stirring for 10 minutes, TPC was further added in a manner that was 27.27 mol% relative to TFMB, and stirred for 30 minutes. Then, an amount of DMAc equal to the DMAc added first was added, and after stirring for 10 minutes, TPC was added in a manner that was 6.06 mol% relative to TFMB, and stirred for 2 hours. Next, diisopropylethylamine, 4-methylpyridine and acetic anhydride were added to the flask at 60.61 mol%, 60.61 mol% and 282.83 mol% respectively based on TFMB, and after stirring for 30 minutes, the internal temperature was raised to 70°C and stirred for further 3 hours to obtain a reaction solution.
[0363] The obtained reaction solution was cooled to room temperature, and the reaction solution was put into a large amount of methanol in a thread form, and the precipitate was taken out, immersed in methanol for 6 hours, and then washed with methanol. Next, the precipitate was dried under reduced pressure at 60°C to obtain a polyamide-imide resin (1). The Mw of the obtained polyamide-imide resin (1) was 748,000.
[0364] <Synthesis Example 2: Production of polyamide-imide resin (2)>
[0365] In a nitrogen atmosphere, TFMB and DMAc that was strictly dehydrated to a water content of less than 700 ppm were added to a separable flask equipped with a stirring blade so that the solid content of TFMB was 5.27% by mass, and TFMB was dissolved in DMAc while stirring at room temperature. Next, 6FDA and an ester of trimellitic anhydride and 4,4'-biphenol were added to the flask so that they were 20.10 mol% respectively relative to TFMB, and stirred at room temperature for 16 hours. Then, after cooling to 10°C, TPC was added in a manner that was 27.14 mol% relative to TFMB, and after stirring for 10 minutes, TPC was further added in a manner that was 27.14 mol% relative to TFMB, and stirred for 30 minutes. Then, an equal amount of DMAc to the DMAc added first was added, and after stirring for 10 minutes, TPC was added in a manner that was 6.03 mol% relative to TFMB, and stirred for 2 hours. Next, diisopropylethylamine, 4-methylpyridine and acetic anhydride were added to the flask at 60.30 mol%, 60.30 mol% and 281.41 mol% respectively based on TFMB, and after stirring for 30 minutes, the internal temperature was raised to 70°C and stirred for further 3 hours to obtain a reaction solution.
[0366] The obtained reaction solution was cooled to room temperature and put into a large amount of methanol in a filamentous form. The precipitate was taken out, immersed in methanol for 6 hours, and then washed with methanol. Next, the precipitate was dried under reduced pressure at 60°C to obtain a polyamide-imide resin (2). The Mw of the obtained polyamide-imide resin (2) was 139,000.
[0367] <Synthesis Example 3: Production of polyamide-imide resin (3)>
[0368] Under a nitrogen atmosphere, TFMB and DMAc that was strictly dehydrated to a water content of less than 700 ppm were added to a separable flask equipped with a stirring blade so that the solid content of TFMB was 5.35% by mass, and TFMB was dissolved in DMAc while stirring at room temperature. Next, 6FDA was added to the flask so that it was 41.24 mol% relative to TFMB, and stirred at room temperature for 16 hours. Then, after cooling to 10°C, TPC was added in a manner that it was 27.84 mol% relative to TFMB, and after stirring for 10 minutes, TPC was further added in a manner that it was 27.84 mol% relative to TFMB, and stirred for 30 minutes. Then, an equal amount of DMAc to the DMAc added first was added, and after stirring for 10 minutes, TPC was added in a manner that it was 6.19 mol% relative to TFMB, and stirred for 2 hours. Next, diisopropylethylamine, 4-methylpyridine and acetic anhydride were added to the flask at 61.86 mol%, 61.86 mol% and 288.66 mol% respectively based on TFMB, and after stirring for 30 minutes, the internal temperature was raised to 70°C and stirred for further 3 hours to obtain a reaction solution.
[0369] The obtained reaction solution was cooled to room temperature and put into a large amount of methanol in a filamentous form. The precipitate was taken out, immersed in methanol for 6 hours, and then washed with methanol. Next, the precipitate was dried under reduced pressure at 60°C to obtain a polyamide-imide resin (3). The Mw of the obtained polyamide-imide resin (3) was 174,000.
[0370] <Synthesis Example 5: Production of polyamide-imide resin (5)>
[0371] In a nitrogen atmosphere, TFMB and DMAc strictly dehydrated to a water content of less than 700 ppm were added to a separable flask equipped with a stirring blade, so that the solid content of TFMB was 5.81% by mass, and TFMB was dissolved in DMAc while stirring at room temperature. Next, 6FDA was added to the flask to make it 20.41 mol% relative to TFMB, and stirred at room temperature for 16 hours. Then, after cooling to 10°C, TPC was added in a manner to make it 36.73 mol% relative to TFMB, and after stirring for 10 minutes, TPC was further added in a manner to make it 36.73 mol% relative to TFMB, and stirred for 30 minutes. Then, DMAc was added in an amount equal to the DMAc added first, and after stirring for 10 minutes, TPC was added in a manner to make it 8.16 mol% relative to TFMB, and stirred for 2 hours, but the viscosity increased significantly in the middle, and the solution became agar-like. Since the subsequent synthesis operation became difficult, the resin synthesis was abandoned.
[0372] <Synthesis Example 6: Production of polyamide-imide resin (6)>
[0373] Under a nitrogen atmosphere, TFMB and DMAc that was strictly dehydrated to a water content of less than 700 ppm were added to a separable flask equipped with a stirring blade, so that the solid content of TFMB was 5.44% by mass, and TFMB was dissolved in DMAc while stirring at room temperature. Next, 6FDA was added to the flask so that it was 30.15 mol% relative to TFMB, and stirred at room temperature for 16 hours. Then, after cooling to 10°C, OMTPC was added in a manner that it was 33.08 mol% relative to TFMB, and after stirring for 10 minutes, OMTPC was further added in a manner that it was 33.08 mol% relative to TFMB, and stirred for 30 minutes. Then, an equal amount of DMAc to the DMAc added first was added, and after stirring for 10 minutes, OMTPC was added in a manner that it was 7.04 mol% relative to TFMB, and stirred for 2 hours. Next, diisopropylethylamine, 4-methylpyridine and acetic anhydride were added to the flask at 70.35 mol%, 70.35 mol% and 211.06 mol% respectively based on TFMB, and after stirring for 30 minutes, the internal temperature was raised to 70°C and stirred for further 3 hours to obtain a reaction solution.
[0374] The obtained reaction solution was cooled to room temperature and put into a large amount of methanol in a filamentous form. The precipitate was taken out, immersed in methanol for 6 hours, and then washed with methanol. Next, the precipitate was dried under reduced pressure at 60°C to obtain a polyamide-imide resin (6). The Mw of the obtained polyamide-imide resin (6) was 612,000.
[0375] <Synthesis Example 7: Production of polyamide-imide resin (7)>
[0376] Under a nitrogen atmosphere, TFMB and DMAc that was strictly dehydrated to a water content of less than 700 ppm were added to a separable flask equipped with a stirring blade, so that the solid content of TFMB was 5.63% by mass, and TFMB was dissolved in DMAc while stirring at room temperature. Next, 6FDA was added to the flask so that it was 20.20 mol% relative to TFMB, and stirred at room temperature for 16 hours. Then, after cooling to 10°C, DMTPC was added in a manner that it was 36.36 mol% relative to TFMB, and after stirring for 10 minutes, DMTPC was further added in a manner that it was 36.36 mol% relative to TFMB, and stirred for 30 minutes. Then, an amount of DMAc equal to the DMAc added first was added, and after stirring for 10 minutes, DMTPC was added in a manner that it was 8.08 mol% relative to TFMB, and stirred for 2 hours. Next, diisopropylethylamine, 4-methylpyridine and acetic anhydride were added to the flask so as to be 80.81 mol%, 80.81 mol% and 141.41 mol% respectively based on TFMB, and after stirring for 30 minutes, the internal temperature was raised to 70°C and stirred for further 3 hours to obtain a reaction solution.
[0377] The obtained reaction solution was cooled to room temperature and put into a large amount of methanol in a filamentous form. The precipitate was taken out, immersed in methanol for 6 hours, and then washed with methanol. Next, the precipitate was dried under reduced pressure at 60°C to obtain a polyamide-imide resin (7). The Mw of the obtained polyamide-imide resin (7) was 482,000.
[0378] <Synthesis Example 8: Production of polyamide-imide resin (8)>
[0379] Under a nitrogen atmosphere, TFMB and DMAc that was strictly dehydrated to a water content of less than 700 ppm were added to a separable flask equipped with a stirring blade, so that the solid content of TFMB was 5.63% by mass, and TFMB was dissolved in DMAc while stirring at room temperature. Next, 6FDA was added to the flask so that it was 20.10 mol% relative to TFMB, and stirred at room temperature for 16 hours. Then, after cooling to 10°C, OMTPC was added in a manner that it was 36.18 mol% relative to TFMB, and after stirring for 10 minutes, OMTPC was further added in a manner that it was 36.18 mol% relative to TFMB, and stirred for 30 minutes. Then, an amount of DMAc equal to the DMAc added first was added, and after stirring for 10 minutes, OMTPC was added in a manner that it was 8.04 mol% relative to TFMB, and stirred for 2 hours. Next, diisopropylethylamine, 4-methylpyridine and acetic anhydride were added to the flask to give 80.40 mol%, 80.40 mol% and 140.70 mol% respectively based on TFMB, and the mixture was stirred for 30 minutes. The internal temperature was then raised to 70°C and stirred for further 3 hours to obtain a reaction solution.
[0380] The obtained reaction solution was cooled to room temperature and put into a large amount of methanol in a filamentous form. The precipitate was taken out, immersed in methanol for 6 hours, and then washed with methanol. Next, the precipitate was dried under reduced pressure at 60°C to obtain a polyamide-imide resin (8). The Mw of the obtained polyamide-imide resin (8) was 483,000.
[0381] <Synthesis Example 9: Production of polyamide-imide resin (9)>
[0382] Under a nitrogen atmosphere, TFMB and DMAc that was strictly dehydrated to a water content of less than 700 ppm were added to a separable flask equipped with a stirring blade so that the solid content of TFMB was 5.52% by mass, and TFMB was dissolved in DMAc while stirring at room temperature. Next, 6FDA and BPDA were added to the flask so that they were 20.10 mol% respectively relative to TFMB, and stirred at room temperature for 16 hours. Then, after cooling to 10°C, OMTPC was added in a manner that was 27.14 mol% relative to TFMB, and after stirring for 10 minutes, OMTPC was further added in a manner that was 27.14 mol% relative to TFMB, and stirred for 30 minutes. Then, an amount of DMAc equal to the DMAc added first was added, and after stirring for 10 minutes, OMTPC was added in a manner that was 6.03 mol% relative to TFMB, and stirred for 2 hours. Next, diisopropylethylamine, 4-methylpyridine and acetic anhydride were added to the flask at 60.30 mol%, 60.30 mol% and 281.41 mol% respectively based on TFMB, and after stirring for 30 minutes, the internal temperature was raised to 70°C and stirred for further 3 hours to obtain a reaction solution.
[0383] The obtained reaction solution was cooled to room temperature and put into a large amount of methanol in a filamentous form. The precipitate was taken out, immersed in methanol for 6 hours, and then washed with methanol. Next, the precipitate was dried under reduced pressure at 60°C to obtain a polyamide-imide resin (9). The Mw of the obtained polyamide-based resin (9) was 594,000.
[0384] <Synthesis Example 10: Production of polyamide-imide resin (10)>
[0385] Under a nitrogen atmosphere, TFMB and DMAc that was strictly dehydrated to a water content of less than 700 ppm were added to a separable flask equipped with a stirring blade, so that the solid content of TFMB was 5.08% by mass, and TFMB was dissolved in DMAc while stirring at room temperature. Next, 6FDA and TahmbP were added to the flask so that they were 20.62 mol% respectively relative to TFMB, and stirred at room temperature for 16 hours. Then, after cooling to 10°C, TPC was added in a manner that was 27.84 mol% relative to TFMB, and after stirring for 10 minutes, TPC was further added in a manner that was 27.84 mol% relative to TFMB, and stirred for 30 minutes. Then, an equal amount of DMAc to the DMAc added first was added, and after stirring for 10 minutes, TPC was added in a manner that was 6.19 mol% relative to TFMB, and stirred for 2 hours. Next, diisopropylethylamine, 4-methylpyridine and acetic anhydride were added to the flask at 61.86 mol%, 61.86 mol% and 288.66 mol% respectively based on TFMB, and after stirring for 30 minutes, the internal temperature was raised to 70°C and stirred for further 3 hours to obtain a reaction solution.
[0386] The obtained reaction solution was cooled to room temperature, and the reaction solution was put into a large amount of methanol in a thread form, and the precipitate was taken out, immersed in methanol for 6 hours, and then washed with methanol. Next, the precipitate was dried under reduced pressure at 60°C to obtain a polyamide-imide resin (10). The Mw of the obtained polyamide-imide resin (10) was 486,000.
[0387] <Synthesis Example 12: Production of polyamide-imide resin (12)>
[0388] Under a nitrogen atmosphere, TFMB and DMAc that was strictly dehydrated to a water content of less than 700 ppm were added to a separable flask equipped with a stirring blade, so that the solid content of TFMB was 5.16% by mass, and TFMB was dissolved in DMAc while stirring at room temperature. Next, THAMBP was added to the flask so that it was 30.61 mol% relative to TFMB, and stirred at room temperature for 16 hours. Then, after cooling to 10°C, TPC was added in a manner that it was 32.14 mol% relative to TFMB, and after stirring for 10 minutes, TPC was further added in a manner that it was 32.14 mol% relative to TFMB, and stirred for 30 minutes. Then, an equal amount of DMAc to the DMAc added first was added, and after stirring for 10 minutes, TPC was added in a manner that it was 7.14 mol% relative to TFMB, and stirred for 2 hours. Next, diisopropylethylamine, 4-methylpyridine and acetic anhydride were added to the flask at 71.43 mol%, 71.43 mol% and 214.29 mol% respectively based on TFMB, and after stirring for 30 minutes, the internal temperature was raised to 70°C and stirred for further 3 hours to obtain a reaction solution.
[0389] The obtained reaction solution was cooled to room temperature, and the reaction solution was put into a large amount of methanol in a thread form, and the precipitate was taken out, immersed in methanol for 6 hours, and then washed with methanol. Next, the precipitate was dried under reduced pressure at 60°C to obtain a polyamide-imide resin (12). The Mw of the obtained polyamide-imide resin (12) was 764,000.
[0390] <Synthesis Example 13: Production of polyamide-imide resin (13)>
[0391] Under a nitrogen atmosphere, TFMB and DMAc that was strictly dehydrated to a water content of less than 700 ppm were added to a separable flask equipped with a stirring blade, so that the solid content of TFMB was 4.86% by mass, and TFMB was dissolved in DMAc while stirring at room temperature. Next, THAMBP was added so that it became 40.82 mol% relative to TFMB, and stirred at room temperature for 16 hours. Then, after cooling to 10°C, TPC was added in a manner that became 27.55 mol% relative to TFMB, and after stirring for 10 minutes, TPC was further added in a manner that became 27.55 mol% relative to TFMB, and stirred for 30 minutes. Then, an amount of DMAc equal to the DMAc added first was added, and after stirring for 10 minutes, TPC was added in a manner that became 6.12 mol% relative to TFMB, and stirred for 2 hours. Next, diisopropylethylamine, 4-methylpyridine and acetic anhydride were added to the flask at 61.22 mol%, 61.22 mol% and 285.71 mol% respectively based on TFMB, and after stirring for 30 minutes, the internal temperature was raised to 70°C and stirred for further 3 hours to obtain a reaction solution.
[0392] The obtained reaction solution was cooled to room temperature, and the reaction solution was put into a large amount of methanol in a filamentous form. The precipitate was taken out, immersed in methanol for 6 hours, and then washed with methanol. Next, the precipitate was dried under reduced pressure at 60° C. to obtain a polyamide-imide resin (13). The Mw of the obtained polyamide-imide resin (13) was 613,000.
[0393] <Synthesis Example 14: Production of polyamide-imide resin (14)>
[0394] Under a nitrogen atmosphere, TFMB and DMAc that was strictly dehydrated to a water content of less than 700 ppm were added to a separable flask equipped with a stirring blade so that the solid content of TFMB was 5.29% by mass, and TFMB was dissolved in DMAc while stirring at room temperature. Next, 6FDA and TahmbP were added to the flask so that they were 10.20 mol% and 20.41 mol% respectively relative to TFMB, and stirred at room temperature for 16 hours. Then, after cooling to 10°C, TPC was added in a manner that was 32.14 mol% relative to TFMB, and after stirring for 10 minutes, TPC was further added in a manner that was 32.14 mol% relative to TFMB, and stirred for 30 minutes. Then, an equal amount of DMAc to the DMAc added first was added, and after stirring for 10 minutes, TPC was added in a manner that was 7.14 mol% relative to TFMB, and stirred for 2 hours. Next, diisopropylethylamine, 4-methylpyridine and acetic anhydride were added to the flask at 71.43 mol%, 71.43 mol% and 214.29 mol% respectively based on TFMB, and after stirring for 30 minutes, the internal temperature was raised to 70°C and stirred for further 3 hours to obtain a reaction solution.
[0395] The obtained reaction solution was cooled to room temperature, and the reaction solution was put into a large amount of methanol in a thread form, and the precipitate was taken out, immersed in methanol for 6 hours, and then washed with methanol. Next, the precipitate was dried under reduced pressure at 60°C to obtain a polyamide-imide resin (14). The Mw of the obtained polyamide-imide resin (14) was 751,000.
[0396] <Example 1>
[0397] The polyamide-imide resin (1) obtained in Synthesis Example 1 and DMAc were mixed in an amount such that the content of the polyamide-imide resin in the resin composition was 10% by mass. The obtained resin composition was applied to the smooth surface of a polyester substrate (manufactured by Toyobo Co., Ltd., trade name "A4100") using an applicator in such a manner that the thickness of the self-supporting film was 55 μm, and dried at 50° C. for 30 minutes, and then dried at 140° C. for 15 minutes, and then the obtained coating was peeled off from the polyester substrate to obtain a self-supporting film. The self-supporting film was fixed to a metal frame and further dried at 200° C. for 40 minutes in the atmosphere to obtain a polyamide-imide resin film (1) having a thickness of 50 μm.
[0398] <Example 2>
[0399] The polyamideimide resin (6) obtained in Synthesis Example 6 and DMAc were mixed in such an amount that the content of the polyamideimide resin in the resin composition became 10 mass %. Using the obtained resin composition, the same operation as in Example 1 was carried out to obtain a polyamideimide resin film (6) having a thickness of 38 μm.
[0400] <Example 3>
[0401] The polyamideimide resin (7) obtained in Synthesis Example 7 and DMAc were mixed in such an amount that the content of the polyamideimide resin in the resin composition became 10 mass %. Using the obtained resin composition, the same operation as in Example 1 was carried out to obtain a polyamideimide resin film (7) having a thickness of 42 μm.
[0402] <Example 4>
[0403] The polyamideimide resin (8) obtained in Synthesis Example 8 and DMAc were mixed in such an amount that the content of the polyamideimide resin in the resin composition became 10 mass %. Using the obtained resin composition, the same operation as in Example 1 was carried out to obtain a polyamideimide resin film (8) having a thickness of 40 μm.
[0404] <Example 5>
[0405] The polyamideimide resin (9) obtained in Synthesis Example 9 and DMAc were mixed in such an amount that the content of the polyamideimide resin in the resin composition became 10 mass %. Using the obtained resin composition, the same operation as in Example 1 was carried out to obtain a polyamideimide resin film (9) having a thickness of 40 μm.
[0406] <Example 6>
[0407] The polyamideimide resin (10) obtained in Synthesis Example 10 and DMAc were mixed in such an amount that the content of the polyamideimide resin in the resin composition became 10 mass %. Using the obtained resin composition, the same operation as in Example 1 was carried out to obtain a polyamideimide resin film (10) having a thickness of 40 μm.
[0408] <Example 8>
[0409] The polyamideimide resin (12) obtained in Synthesis Example 12 and DMAc were mixed in such an amount that the content of the polyamideimide resin in the resin composition became 10 mass %. Using the obtained resin composition, the same operation as in Example 1 was carried out to obtain a polyamideimide resin film (12) having a thickness of 40 μm.
[0410] <Example 9>
[0411] The polyamideimide resin (13) obtained in Synthesis Example 13 and DMAc were mixed in such an amount that the content of the polyamideimide resin in the resin composition became 10 mass %. Using the obtained resin composition, the same operation as in Example 1 was carried out to obtain a polyamideimide resin film (13) having a thickness of 40 μm.
[0412] <Example 10>
[0413] The polyamideimide resin (14) obtained in Synthesis Example 14 and DMAc were mixed in such an amount that the content of the polyamideimide resin in the resin composition became 10 mass %. Using the obtained resin composition, the same operation as in Example 1 was carried out to obtain a polyamideimide resin film (14) having a thickness of 40 μm.
[0414] <Comparative Example 1>
[0415] The polyamideimide resin (2) obtained in Synthesis Example 2 and DMAc were mixed in such an amount that the content of the polyamideimide resin in the resin composition became 10 mass %. Using the obtained resin composition, the same operation as in Example 1 was carried out to obtain a polyamideimide resin film (2) having a thickness of 50 μm.
[0416] <Comparative Example 2>
[0417] The polyamideimide resin (3) obtained in Synthesis Example 3 and DMAc were mixed in such an amount that the content of the polyamideimide resin in the resin composition became 10 mass %. Using the obtained resin composition, the same operation as in Example 1 was carried out to obtain a polyamideimide resin film (3) having a thickness of 50 μm.
[0418] The yield strength, elastic modulus, total light transmittance, haze, YI value and folding endurance times of the polyamide-imide resin films of the examples and comparative examples obtained as described above were measured. The results obtained are shown in Tables 1 and 2. It should be noted that the resin of Synthesis Example 5 became insoluble during the synthesis, and the polyamide-imide resin could not be synthesized, so the measurement and evaluation could not be performed.
[0419] [Table 1]
[0420] Example 1 Example 2 Example 3 Example 4 Example 5 Example 6 Types of resin PAI(1) PAI(6) PAI(7) PAI(8) PAI(9) PAI(10) Yield strength(MPa) 95.4 92.4 100.5 98.1 111.9 90.8 Elastic modulus(GPa) 6.24 6.00 6.35 6.70 6.80 5.99 Total light transmittance (%) 91.4 91.3 91.5 91.3 90.9 89.0 Haze(%) 0.3 0.3 0.3 0.3 0.1 0.2 YI value 2.44 2.43 1.61 2.30 2.66 2.27 Folding times (times) 254,000 336,000 90,000 122,000 153,000 111,000
[0421] [Table 2]
[0422] Example 8 Example 9 Example 10 Comparative Example 1 Comparative Example 2 Types of resin PAI(12) PAI(13) PAI(14) PAI(2) PAI(3) Yield strength(MPa) 105.1 91.6 106.6 77.1 72.0 Elastic modulus(GPa) 7.02 5.43 6.56 5.88 4.71 Total light transmittance (%) 88.4 89.1 88.7 88 91.8 Haze(%) 0.3 0.3 0.2 3.25 0.2 YI value 2.49 2.55 2.57 18.11 1.56 Folding times (times) 377,000 146,000 241,000 11,000 75,000
[0423] As shown in Tables 1 and 2, the optical films of Examples 1 to 6 and 8 to 10 were confirmed to have low YI values, high yield strength, and excellent folding resistance. In addition, they were also confirmed to have high transparency. In contrast, the optical films of Comparative Examples 1 and 2 had low yield strength and insufficient folding resistance.
Claims
1. An optical film comprising a polyimide resin, The weight average molecular weight of the polyimide resin is 100,000 or more, and the polyimide resin includes a structural unit represented by the following formula (1): The optical film has a yield strength of 81 MPa or more, an elastic modulus of 4.8 GPa or more, and a yellowness of less than 3.0 in a tensile test. In formula (1), Y represents a tetravalent organic group, X represents a divalent organic group, and * represents a bonding end. Y in formula (1) includes a structure represented by the following formula (2): In formula (2), R 1 independently represent a halogen atom, an alkyl group, an alkoxy group, an aryl group or an aryloxy group which may have a halogen atom, and R 2 ~R 5 Each of the following independently represents a hydrogen atom or a monovalent hydrocarbon group optionally having a halogen atom; each of the following independently represents an integer of 0 to 3; each of the following independently represents an integer of 1 to 4; each ... In the case of R 2 ~R 5 In at least one benzene ring, R 2 ~R 5 At least one of them is a monovalent hydrocarbon group which may have a halogen atom.
2. The optical film according to claim 1, wherein the total light transmittance is greater than 85%.
3. The optical film according to claim 1 or 2, wherein: The polyimide-based resin is a polyamide-imide resin.
4. The optical film according to claim 1 or 2, wherein: The polyimide resin comprises a structural unit represented by formula (3), In formula (3), Z and X independently represent a divalent organic group, and * represents a bonding end.
5. The optical film according to claim 4, wherein: In the polyimide resin, Z in the formula (3) includes a structure represented by the formula (4), In formula (4), W independently represents a single bond, -O-, diphenylmethylene, a divalent hydrocarbon group optionally having a halogen atom, -SO2-, -S-, -CO-, -PO-, -PO2-, -N(R W1 )-or-Si(R W2 )2-, R W1 and R W2 independently represent a hydrogen atom or an alkyl group optionally having a halogen atom, R 8 Each of them independently represents a halogen atom, an alkyl group which may have a halogen atom, an alkoxy group, an aryl group or an aryloxy group, each of them independently represents an integer of 0 to 4, each of them independently represents an integer of 0 to 4, and * represents a bonding end. The optical film according to claim 1 or 2, which is a film for a front panel of a flexible display device. 7 . A flexible display device comprising the optical film according to claim 1 . The flexible display device according to claim 7 , further comprising a touch sensor. 9 . The flexible display device according to claim 7 , further comprising a polarizing plate.
